Resin composition
By optimizing the combination of maleimide resin, anionic polymerizable hardener, imidazole catalyst and inorganic filler, the problem of insufficient dielectric loss and mechanical strength in the insulating layer of the resin composition is solved, and a resin composition with low dielectric loss tangent, high mechanical strength and good copper adhesion is achieved.
Patent Information
- Application Number
- JP2023123291
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-28
- Publication Date
- 2025-02-07
AI Technical Summary
When the conventional resin composition forms an insulating layer, it is difficult to achieve a low dielectric loss tangent and high mechanical strength at the same time, and the adhesion to copper is insufficient.
The resin composition containing maleimide resin, anionic polymerizable hardener, imidazole catalyst and inorganic filler is adopted to ensure that the content of inorganic filler reaches more than 50% of the total non-volatile parts, and the ratio of maleimide groups to anionic polymerizable hardener is controlled, and a small amount of epoxy resin is added to form a cured product with low dielectric loss tangent and high mechanical strength.
Achieves low dielectric loss tangent and high mechanical strength cured products while improving adhesion with copper.
Smart Images

Figure 2025019602000001 
Figure 2025019602000002 
Figure 2025019602000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition containing a maleimide resin and an inorganic filler, and further to a resin sheet, a printed wiring board, and a semiconductor device obtained by using the resin composition. [Background technology]
[0002] A known manufacturing technique for printed wiring boards is a build-up method in which insulating layers and conductor layers are alternately stacked. In the build-up method, the insulating layers are generally formed by curing a resin composition containing a maleimide resin and an inorganic filler.
[0003] Printed wiring boards are required to have a low dielectric loss tangent in order to reduce transmission loss. At the same time, materials with excellent mechanical strength are also required to improve the reliability of printed wiring boards. However, resin compositions for forming insulating layers to date have not been sufficiently low in dielectric loss tangent or high in mechanical strength (Patent Documents 1 to 3). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2014-521754 A [Patent Document 2] Patent No. 6379675 [Patent Document 3] Patent No. 6992333 Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to provide a resin composition which can give a cured product having a low dielectric tangent and excellent mechanical strength and copper adhesion. [Means for solving the problem]
[0006] In order to achieve the objects of the present invention, the present inventors have conducted intensive research and have unexpectedly found that a cured product having a low dielectric tangent and excellent mechanical strength and copper adhesion can be obtained by using a resin composition comprising (A) a maleimide resin, (B) an anionic polymerizable curing agent, (C) an imidazole-based curing catalyst, and (D) an inorganic filler, wherein the content of component (D) is 50% by mass or more when the total non-volatile components in the resin composition is taken as 100% by mass, the maleimide groups of component (A) are 0.1 to 100 molar equivalents per molar equivalent of reactive groups of component (B), and the content of (E) epoxy resin is 0 to 1 mass% when the total non-volatile components in the resin composition excluding component (D) is taken as 100% by mass, thereby completing the present invention.
[0007] That is, the present invention includes the following. [1] A resin composition comprising: (A) a maleimide resin; (B) an anionic polymerizable curing agent; (C) an imidazole-based curing catalyst; and (D) an inorganic filler, The content of the (D) component is 50% by mass or more, relative to 100% by mass of all non-volatile components in the resin composition; the amount of maleimide groups in the component (A) is 0.1 to 100 molar equivalents relative to 1 molar equivalent of reactive groups in the component (B); A resin composition having an epoxy resin content of (E) 0 to 1% by mass, where the total non-volatile components in the resin composition excluding the component (D) is taken as 100% by mass. [2] The resin composition according to the above [1], wherein the maleimide group equivalent of the component (A) is 100 g / eq. to 500 g / eq. [3] The resin composition according to the above [1] or [2], wherein the component (A) contains a maleimide resin selected from the group consisting of maleimide resins having a biphenyl skeleton, maleimide resins having an indane skeleton, maleimide resins having a bismaleimide diphenylmethane skeleton, maleimide resins having a carbon skeleton derived from dimer acid, and maleimide resins having an aromatic polyether ketone skeleton. [4] The resin composition according to any one of the above [1] to [3], wherein the content of the component (A) is 30 mass% or more, based on 100 mass% of the non-volatile components in the resin composition excluding the component (D). [5] The resin composition according to any one of the above [1] to [4], wherein the component (B) contains an anion-polymerizable curing agent selected from a phenol-based curing agent, a carbodiimide-based curing agent, an amine-based curing agent, a benzoxazine-based curing agent, and an active ester-based curing agent. [6] The resin composition according to any one of the above [1] to [5], wherein the component (B) contains a phenol-based curing agent. [7] The resin composition according to any one of the above [1] to [6], wherein the content of the (B) component is 25 mass% or less, based on 100 mass% of non-volatile components in the resin composition excluding the (D) component. [8] The resin composition according to any one of the above [1] to [7], wherein a mass ratio of the component (B) to the component (A) (component (B) / component (A)) is 0.05 to 1. [9] The resin composition according to any one of the above [1] to [8], wherein the content of the component (C) is 1 to 5 mass % relative to 100 mass % of the non-volatile components in the resin composition excluding the component (D).
[10] The resin composition according to any one of the above [1] to [9], wherein the component (D) contains silica.
[11] The resin composition according to any one of the above [1] to
[10] , further comprising (F) an ethylenically unsaturated bond-containing resin.
[12] The resin composition according to any one of the above [1] to
[11] , further comprising a thermoplastic resin (G).
[13] The resin composition according to any one of [1] to
[12] above, wherein, when a tensile strength measurement is performed in accordance with JIS K7127, the strength at break of a cured product of the resin composition is 100 MPa or more, and the elongation at break of the cured product of the resin composition is 1.5% or more.
[14] The resin composition according to any one of the above [1] to
[13] , wherein the glass transition temperature (Tg) of a cured product of the resin composition is 140° C. or higher.
[15] The resin composition according to any one of the above [1] to
[14] , wherein a dielectric loss tangent (Df) of a cured product of the resin composition is 0.004 or less when measured at 5.8 GHz and 23°C.
[16] The resin composition according to any one of the above [1] to
[15] , wherein a cured product of the resin composition has a relative dielectric constant (Dk) of 3.2 or less when measured at 5.8 GHz and 23°C.
[17] A cured product of the resin composition according to any one of [1] to
[16] above.
[18] A resin sheet comprising: a support; and a resin composition layer formed on the support, the resin composition being formed from the resin composition according to any one of [1] to
[16] above.
[19] A printed wiring board comprising an insulating layer made of a cured product of the resin composition according to any one of [1] to
[16] above.
[20] A semiconductor device comprising the printed wiring board described in
[19] above. Effect of the Invention
[0008] According to the resin composition of the present invention, it is possible to obtain a cured product having a low dielectric tangent and excellent mechanical strength and copper adhesion. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The present invention will be described in detail below with reference to preferred embodiments. However, the present invention is not limited to the following embodiments and examples, and can be modified and implemented as desired without departing from the scope of the claims of the present invention and their equivalents.
[0010] <Resin composition> The resin composition of the present invention comprises (A) a maleimide resin, (B) an anionic polymerizable curing agent, (C) an imidazole-based curing catalyst, and (D) an inorganic filler, the content of the (D) component being 50% by mass or more when the total nonvolatile components in the resin composition are taken as 100% by mass, the maleimide group of the (A) component is 0.1 to 100 molar equivalents per molar equivalent of the reactive group of the (B) component, and the content of the (E) epoxy resin being 0 to 1% by mass when the total nonvolatile components in the resin composition excluding the (D) component are taken as 100% by mass. With such a resin composition, a cured product having a low dielectric tangent and excellent mechanical strength and copper adhesion can be obtained.
[0011] The resin composition of the present invention may further contain optional components in addition to (A) the maleimide resin, (B) the anionic polymerizable curing agent, (C) the imidazole-based curing catalyst, and (D) the inorganic filler, such as (E) an epoxy resin, (F) an ethylenically unsaturated bond-containing resin, (G) a thermoplastic resin, (H) a radical polymerization initiator, (I) other additives, and (J) an organic solvent.
[0012] Each component contained in the resin composition will be described in detail below.
[0013] <(A) Maleimide resin> The resin composition of the present invention contains (A) a maleimide resin. (A) The maleimide resin may be used alone or in combination of two or more. (A) The maleimide resin has one or more maleimide groups (2,5-dihydro-2,5-dioxo-1H-pyrrol-1-yl groups) in one molecule.
[0014] The (A) maleimide resin can be an aromatic maleimide resin having a maleimide group directly bonded to an aromatic ring, or an aliphatic maleimide resin having no maleimide group directly bonded to an aromatic ring, but preferably comprises an aromatic maleimide resin.
[0015] The (A) maleimide resin preferably contains a maleimide resin selected from the group consisting of maleimide resins having a biphenyl skeleton, maleimide resins having an indane skeleton, maleimide resins having a bismaleimide diphenylmethane skeleton, maleimide resins having a carbon skeleton derived from dimer acid, and maleimide resins having an aromatic polyether ketone skeleton.
[0016] The carbon skeleton derived from dimer acid is the carbon skeleton of dimer acid excluding the two terminal carboxyl groups (-COOH), or the carbon skeleton of dimer acid excluding the two terminal carboxyl groups (-COOH) and the methylene groups (-CH 2-) is substituted. Dimer acid is a known compound obtained by dimerizing unsaturated fatty acids (preferably those having 11 to 22 carbon atoms, more preferably those having 14 to 20 carbon atoms, and particularly preferably those having 18 carbon atoms), and its industrial production process is almost standardized in the industry. Dimer acids are easily available, especially those containing dimer acids having 36 carbon atoms as the main component obtained by dimerizing unsaturated fatty acids having 18 carbon atoms, such as oleic acid and linoleic acid, which are inexpensive and easily available. In addition, dimer acids may contain any amount of monomer acids, trimer acids, other polymerized fatty acids, etc., depending on the production method, degree of purification, etc. In addition, double bonds remain after the polymerization reaction of unsaturated fatty acids, but in this specification, hydrogenated products in which the degree of unsaturation is reduced by further hydrogenation reaction are also included in dimer acids.
[0017] Maleimide resins having a carbon skeleton derived from dimer acid have the formula (1):
[0018] [ka]
[0019] [In the formula, n+1 X's each independently represent a divalent organic group consisting of five or more skeletal atoms selected from carbon atoms, nitrogen atoms (not forming an imide), oxygen atoms, and sulfur atoms, and non-skeletal atoms selected from hydrogen atoms and halogen atoms, and at least one of the n+1 X's represents a divalent hydrocarbon group derived from a dimer acid; n Y's each independently represent a tetravalent organic group having five or more skeletal atoms selected from carbon atoms, nitrogen atoms (not forming an imide), oxygen atoms, and sulfur atoms, and non-skeletal atoms selected from hydrogen atoms and halogen atoms; n represents an integer of 0 or 1 or more. It is preferable that the maleimide resin contains a maleimide resin represented by the following formula:
[0020] The n+1 Xs each independently represent a divalent organic group consisting of 5 or more (preferably 5 to 200, more preferably 5 to 100, and even more preferably 5 to 50) skeletal atoms selected from carbon atoms, nitrogen atoms (not forming an imide), oxygen atoms, and sulfur atoms, and non-skeletal atoms selected from hydrogen atoms and halogen atoms, and at least one of the n+1 Xs represents a divalent hydrocarbon group derived from a dimer acid.
[0021] The halogen atom is a fluorine atom, a chlorine atom, a bromine atom, or an iodine atom.
[0022] A divalent hydrocarbon group derived from a dimer acid is a divalent hydrocarbon group obtained by removing the two terminal carboxy groups (-COOH) of a dimer acid, or a divalent hydrocarbon group obtained by converting the two terminal carboxy groups (-COOH) into a methylene group (-CH 2 -) is substituted with a divalent hydrocarbon group.
[0023] The n+1 X's may have a divalent organic group other than a divalent hydrocarbon group derived from a dimer acid, but when the n+1 X's are taken as 100 mol%, it is preferable that 30 mol% or more of them are divalent hydrocarbon groups derived from a dimer acid, more preferably 60 mol% or more of them are divalent hydrocarbon groups derived from a dimer acid, even more preferably 90 mol% or more of them are divalent hydrocarbon groups derived from a dimer acid, and it is particularly preferable that (all) the n+1 X's are divalent hydrocarbon groups derived from a dimer acid.
[0024] The divalent organic group other than the divalent hydrocarbon group derived from a dimer acid in the n+1 X's may be a divalent organic group not having an aromatic ring, or may be a divalent organic group having an aromatic ring.
[0025] The n Ys each independently represent a tetravalent organic group consisting of 5 or more (preferably 5 to 200, more preferably 5 to 100, and even more preferably 5 to 50) skeletal atoms selected from carbon atoms, nitrogen atoms (not forming imides), oxygen atoms, and sulfur atoms, and non-skeletal atoms selected from hydrogen atoms and halogen atoms. The tetravalent organic group represented by Y may be a tetravalent organic group having no aromatic ring, or may be a tetravalent organic group having an aromatic ring.
[0026] In one embodiment, the tetravalent organic group represented by Y is preferably represented by any one of the formulae (Y1) to (Y5):
[0027] [ka]
[0028] [In the formula, Ring Y 11 , ring Y 21 , ring Y 22 , ring Y 31 , ring Y 32 , ring Y 33 , ring Y 41 , ring Y 42 , ring Y 43 , ring Y 44 , ring Y 51 , ring Y 52 , ring Y 53 , ring Y 54 and ring Y 55 each independently represents an aromatic ring which may have a substituent, or a non-aromatic ring which may have a substituent; Y 2a , Y 3a , Y 3b , Y 4a , Y 4b , Y 4c , Y 5a , Y 5b , Y 5c and Y 5d are each independently a single bond, -C(R y ) 2 -, -O-, -CO-, -S-, -SO-, -SO 2 -, -CONH-, or -NHCO-; Ry each independently represents a hydrogen atom or an alkyl group which may be substituted with a halogen atom, or two R y are linked together to form a non-aromatic ring which may have a substituent; * indicates binding site.] The two bonding sites on the same ring represented by * are bonding sites to two adjacent carbon atoms on the ring.
[0029] Ring Y 11 , ring Y 21 , ring Y 22 , ring Y 31 , ring Y 32 , ring Y 33 , ring Y 41 , ring Y 42 , ring Y 43 , ring Y 44 , ring Y 51 , ring Y 52 , ring Y 53 , ring Y 54 and ring Y 55 each independently represents an aromatic ring which may have a substituent, or a non-aromatic ring which may have a substituent; in one embodiment, it is preferably an aromatic ring which may have a substituent, more preferably a benzene ring which may have a substituent, and even more preferably a benzene ring which may be substituted with an alkyl group.
[0030] The aromatic ring means a ring conforming to the Huckel rule in which the number of electrons contained in the π electron system on the ring is 4p+2 (p is a natural number). The aromatic ring may be an aromatic carbocycle having only carbon atoms as ring-constituting atoms, or an aromatic heterocycle having heteroatoms such as oxygen atoms, nitrogen atoms, and sulfur atoms in addition to carbon atoms as ring-constituting atoms. In one embodiment, the aromatic ring is preferably an aromatic carbocycle. In one embodiment, the aromatic ring is preferably a 5- to 14-membered aromatic ring, more preferably a 6- to 14-membered aromatic ring, and even more preferably a 6- to 10-membered aromatic ring. Suitable specific examples of the aromatic ring (aromatic carbocycle) include a benzene ring, a naphthalene ring, an anthracene ring, and a phenanthrene ring, and more preferably a benzene ring or a naphthalene ring, and particularly preferably a benzene ring.
[0031] The non-aromatic ring means a ring other than an aromatic ring having aromaticity in the entire ring. The non-aromatic ring may be a non-aromatic carbocycle having only carbon atoms as ring-constituting atoms, or a non-aromatic heterocycle having heteroatoms such as oxygen atoms, nitrogen atoms, and sulfur atoms as ring-constituting atoms in addition to carbon atoms. In one embodiment, the non-aromatic ring is preferably a non-aromatic carbocycle. The non-aromatic ring may be a saturated ring or an unsaturated ring. The non-aromatic ring is preferably a 3- to 21-membered non-aromatic ring, more preferably a 4- to 17-membered non-aromatic ring, and even more preferably a 5- to 14-membered non-aromatic ring. Specific preferred examples of the non-aromatic ring (non-aromatic carbon ring) include monocyclic non-aromatic saturated carbon rings such as a cyclobutane ring, a cyclopentane ring, a cyclohexane ring, a cycloheptane ring, and a cyclooctane ring; monocyclic non-aromatic unsaturated carbon rings such as a cyclobutene ring, a cyclopentene ring, a cyclohexene ring, a cycloheptene ring, a cyclooctene ring, a cyclopentadiene ring, and a cyclohexadiene ring; bicyclo[2.2.1]heptane ring (norbornane ring), bicyclo[4.4.0]decane ring (decalin ring), bicyclo[5.3.0]decane ring, bicyclo[4.3.0]nonane ring (hydrindane ring), bicyclo[3.2.1]octane ring, bicyclo[5.4.0]undecane ring, bicyclo[3.3.0]octane ring, bicyclo[3.3.1]nonane ring, tricyclo[5.2.1.0 2,6 ] Decane ring (tetrahydrodicyclopentadiene ring), tricyclo[3.3.1.1 3,7]Decane ring (adamantane ring), tricyclo[6.2.1.0 2,7 ] undecane ring and other bicyclic or higher non-aromatic saturated carbocyclic rings; bicyclo[2.2.1] hept-2-ene ring (norbornene ring), bicyclo[2.2.2] oct-2-ene ring, bicyclo[4.4.0] dec-2-ene ring and other bicyclic or higher non-aromatic unsaturated carbocyclic rings. The non-aromatic ring may be a non-aromatic ring partially condensed with an aromatic ring. Examples of the non-aromatic ring partially condensed with an aromatic ring include an indane ring, an indene ring, a tetralin ring, a 1,2-dihydronaphthalene ring, a 1,4-dihydronaphthalene ring, a fluorene ring, a 9,10-dihydroanthracene ring, and a 9,10-dihydrophenanthrene ring.
[0032] Ring Y 11 , ring Y 21 , ring Y 22 , ring Y 31 , ring Y 32 , ring Y 33 , ring Y 41 , ring Y 42 , ring Y 43 , ring Y 44 , ring Y 51 , ring Y 52 , ring Y 53 , ring Y 54 and ring Y 55 The "substituent" in the "optionally substituted aromatic ring" and the "optionally substituted non-aromatic ring" is not particularly limited, but examples thereof include a halogen atom, -NO 2 , -CN, -COH, -OH, -SH, -NH 2 , -COOH, -R, -COR, -OR, -SR, -SOR, -SO 2 R, -NHR, -NR 2 , -COOR, -OCOR, -CONH 2 , -CONHR, -CONR 2 , -NHCOR, and the like (wherein each R is independently a monovalent hydrocarbon group).
[0033] A monovalent hydrocarbon group is a monovalent hydrocarbon group having one or more (preferably 1 to 50, more preferably 1 to 20) carbon atoms as skeletal atoms and hydrogen atoms as non-skeletal atoms. The monovalent hydrocarbon group may be a monovalent saturated hydrocarbon group or a monovalent unsaturated hydrocarbon group. The monovalent hydrocarbon group may or may not have an aromatic structure. Examples of the monovalent hydrocarbon group include an alkyl group, an alkenyl group, an aryl group, an aralkyl group, and an alkylaryl group.
[0034] The alkyl group means a linear, branched and / or cyclic monovalent aliphatic saturated hydrocarbon group. Unless otherwise specified, the alkyl group is preferably an alkyl group having 1 to 14 carbon atoms, more preferably an alkyl group having 1 to 10 carbon atoms, further preferably an alkyl group having 1 to 6 carbon atoms, and particularly preferably an alkyl group having 1 to 3 carbon atoms. Examples of the alkyl group include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, a pentyl group, an isopentyl group, a sec-pentyl group, a neopentyl group, a tert-pentyl group, a hexyl group, an isohexyl group, a heptyl group, an isoheptyl group, an octyl group, an isooctyl group, a tert-octyl group, a cyclopentyl group, a cyclohexyl group, and a cyclohexylmethyl group.
[0035] The alkenyl group refers to a linear, branched, and / or cyclic monovalent aliphatic unsaturated hydrocarbon group having at least one non-aromatic carbon-carbon double bond. Unless otherwise specified, the alkenyl group is preferably an alkenyl group having 2 to 14 carbon atoms, more preferably an alkenyl group having 2 to 10 carbon atoms, further preferably an alkenyl group having 2 to 6 carbon atoms, and particularly preferably an alkenyl group having 2 or 3 carbon atoms. Examples of alkenyl groups include vinyl groups, propenyl groups (allyl groups, 1-propenyl groups, isopropenyl groups), butenyl groups (1-butenyl groups, crotyl groups, methallyl groups, isocrotyl groups, etc.), pentenyl groups (1-pentenyl groups, etc.), hexenyl groups (1-hexenyl groups, etc.), heptenyl groups (1-heptenyl groups, etc.), octenyl groups (1-octenyl groups, etc.), cyclopentenyl groups (2-cyclopentenyl groups, etc.), and cyclohexenyl groups (3-cyclohexenyl groups).
[0036] The aryl group means a monovalent aromatic hydrocarbon group obtained by removing one hydrogen atom from an aromatic carbon ring. Unless otherwise specified, the aryl group is preferably an aryl group having 6 to 14 carbon atoms, more preferably an aryl group having 6 to 10 carbon atoms. Examples of the aryl group include a phenyl group, a 1-naphthyl group, and a 2-naphthyl group.
[0037] The aralkyl group means an alkyl group substituted with one or more (preferably one) aryl groups. Unless otherwise specified, the aralkyl group is preferably an aralkyl group having 7 to 15 carbon atoms, more preferably an aralkyl group having 7 to 11 carbon atoms. Examples of the aralkyl group include a benzyl group, a phenethyl group, a hydrocinnamyl group, an α-methylbenzyl group, an α-cumyl group, a 1-naphthylmethyl group, and a 2-naphthylmethyl group.
[0038] The alkylaryl group means an aryl group substituted with one or more (preferably one) alkyl groups. Unless otherwise specified, the alkylaryl group is preferably an alkylaryl group having 7 to 15 carbon atoms, more preferably an alkylaryl group having 7 to 11 carbon atoms. Examples of the alkylaryl group include a 4-methylphenyl group, a 3-methylphenyl group, a 2-methylphenyl group, a 4-ethylphenyl group, a 3-ethylphenyl group, a 2-ethylphenyl group, a 4-isopropylphenyl group, a 3-isopropylphenyl group, and a 2-isopropylphenyl group.
[0039] Y 2a , Y 3a , Y 3b , Y 4a , Y 4b , Y 4c , Y 5a , Y 5b , Y 5c and Y 5d are each independently a single bond, -C(R y ) 2 -, -O-, -CO-, -S-, -SO-, -SO 2 -, -CONH-, or -NHCO-; in one embodiment, preferably a single bond, -C(R y ) 2 -, or -O-.
[0040] R y each independently represents a hydrogen atom or an alkyl group which may be substituted with a halogen atom, or two R y are bonded together to form a non-aromatic ring which may have a substituent; in one embodiment, they are preferably a hydrogen atom or an alkyl group which may be substituted with a halogen atom, more preferably a hydrogen atom or a methyl group which may be substituted with a halogen atom, even more preferably a hydrogen atom, a methyl group, or a trifluoromethyl group, and particularly preferably a hydrogen atom or a methyl group.
[0041] R yThe "substituent" in the "non-aromatic ring optionally having a substituent" formed by is not particularly limited, but examples thereof include a halogen atom, -NO 2 , -CN, -COH, -OH, -SH, -NH 2 , -COOH, -R, -COR, -OR, -SR, -SOR, -SO 2 R, -NHR, -NR 2 , -COOR, -OCOR, -CONH 2 , -CONHR, -CONR 2 , -NHCOR, and the like (wherein each R is independently a monovalent hydrocarbon group).
[0042] n represents 0 or an integer of 1 or more; in one embodiment, n is preferably 0 or an integer of 1 to 10, and more preferably 0.
[0043] Commercially available maleimide resins having a carbon skeleton derived from a dimer acid include, for example, “BMI-689”, “BMI-1500”, “BMI-1700”, and “BMI-3000J” manufactured by Designer Molecules, Inc., and “SLK-6895-T90” manufactured by Shin-Etsu Chemical Co., Ltd.
[0044] The maleimide resin having a bismaleimide diphenylmethane skeleton is represented by the formula (2):
[0045] [ka]
[0046] [In the formula, R 10 each independently represents a hydrogen atom or an alkyl group which may be substituted with a halogen atom; each ring D independently represents an aromatic carbocyclic ring which may have a substituent; e represents an integer of 1 or more. The maleimide resin having a bismaleimide diphenylmethane skeleton may be used alone or in combination of two or more kinds in any ratio.
[0047] The "substituent" in ring D is not particularly limited, but examples thereof include a halogen atom, -NO 2 , -CN, -COH, -OH, -SH, -NH 2 , -COOH, -R, -COR, -OR, -SR, -SOR, -SO 2 R, -NHR, -NR 2 , -COOR, -OCOR, -CONH 2 , -CONHR, -CONR 2 , -NHCOR, and the like (wherein each R is independently a monovalent hydrocarbon group).
[0048] R 10 each independently represents a hydrogen atom or an alkyl group which may be substituted with a halogen atom, is preferably a hydrogen atom or an alkyl group, is more preferably a hydrogen atom or a methyl group, and is even more preferably a hydrogen atom.
[0049] Each ring D independently represents an aromatic ring which may have a substituent, is preferably a benzene ring which may have a substituent, is more preferably a benzene ring which may be substituted with a group selected from an alkyl group and an aryl group, and is particularly preferably an (unsubstituted) benzene ring.
[0050] e represents an integer of 1 or more, and is preferably an integer of 1 to 10.
[0051] An example of a commercially available maleimide resin having a bismaleimide diphenylmethane skeleton is "BMI-2300" manufactured by Daiwa Chemical Industry Co., Ltd.
[0052] The maleimide resin having a biphenyl skeleton is represented by the formula (3):
[0053] [ka]
[0054] [In the formula, R 20 each independently represents a hydrogen atom or an alkyl group which may be substituted with a halogen atom; Ring E, ring F and ring G each independently represent an aromatic carbocyclic ring which may have a substituent; f is an integer equal to or greater than 1. The maleimide resin having a biphenyl skeleton may be used alone or in combination of two or more kinds in any ratio.
[0055] The "substituents" in rings E, F and G are not particularly limited, but examples thereof include halogen atoms, -NO 2 , -CN, -COH, -OH, -SH, -NH 2 , -COOH, -R, -COR, -OR, -SR, -SOR, -SO 2 R, -NHR, -NR 2 , -COOR, -OCOR, -CONH 2 , -CONHR, -CONR 2 , -NHCOR, and the like (wherein each R is independently a monovalent hydrocarbon group).
[0056] R 20 each independently represents a hydrogen atom or an alkyl group which may be substituted with a halogen atom, is preferably a hydrogen atom or an alkyl group, is more preferably a hydrogen atom or a methyl group, and is even more preferably a hydrogen atom.
[0057] Ring E, ring F and ring G each independently represent an aromatic ring which may have a substituent, preferably a benzene ring which may have a substituent, more preferably a benzene ring which may be substituted with a group selected from an alkyl group and an aryl group, and particularly preferably an (unsubstituted) benzene ring.
[0058] f represents an integer of 1 or more, and is preferably an integer of 1-10.
[0059] Commercially available maleimide resins having a biphenyl skeleton include, for example, "MIR-3000-70MT" and "MIR-5000-60T" manufactured by Nippon Kayaku Co., Ltd.
[0060] The maleimide resin having an indane skeleton is represented by the formula (4):
[0061] [ka]
[0062] [In the formula, R 30 each independently represents an alkyl group; Ring H and ring I each independently represent an aromatic carbocyclic ring which may have a substituent; m represents an integer of 1 or more. It is preferable that the maleimide resin contains a maleimide resin represented by the following formula: The m units may be the same or different from each other.
[0063] The "substituents" in ring H and ring I are not particularly limited, but examples thereof include halogen atoms, -NO 2 , -CN, -COH, -OH, -SH, -NH 2 , -COOH, -R, -COR, -OR, -SR, -SOR, -SO 2 R, -NHR, -NR 2 , -COOR, -OCOR, -CONH 2 , -CONHR, -CONR 2, -NHCOR, and the like (wherein each R is independently a monovalent hydrocarbon group).
[0064] R 30 each independently represents an alkyl group, and in one embodiment, is preferably a methyl group.
[0065] Each ring H independently represents an aromatic ring which may have a substituent, and in one embodiment, is preferably a benzene ring which may have a substituent, more preferably a benzene ring which may be substituted with an alkyl group, and even more preferably a benzene ring substituted with an alkyl group.
[0066] Each ring I independently represents an aromatic ring which may have a substituent, and in one embodiment, it is preferably a benzene ring which may have a substituent, more preferably a benzene ring which may be substituted with an alkyl group, and even more preferably an (unsubstituted) benzene ring.
[0067] m represents an integer of 1 or more, and is preferably an integer of 1-20.
[0068] The maleimide resin having an indane skeleton can be produced, for example, by the method described in the Japan Institute of Invention and Innovation's Technical Journal Publication No. 2020-500211 or a method equivalent thereto.
[0069] The maleimide group equivalent of the (A) maleimide resin is preferably 50 g / eq. or more, more preferably 100 g / eq. or more, even more preferably 150 g / eq. or more, even more preferably 200 g / eq. or more, even more preferably 250 g / eq. or more, and particularly preferably 300 g / eq. or more, and the upper limit is preferably 2,000 g / eq. or less, more preferably 1,000 g / eq. or less, even more preferably 800 g / eq. or less, even more preferably 600 g / eq. or less, even more preferably 500 g / eq. or less, and particularly preferably 450 g / eq. or less. The maleimide group equivalent is the mass of the (A) maleimide resin per 1 molar equivalent of maleimide groups.
[0070] The molecular weight of the (A) maleimide resin is preferably less than 5,000, more preferably less than 3,000, even more preferably less than 2,000, still more preferably less than 1,500, even more preferably less than 1,200, and particularly preferably less than 1,000. The lower limit is not particularly limited, but can be, for example, 300 or more, 400 or more, 500 or more, etc.
[0071] The content of the maleimide resin (A) in the resin composition is preferably 10% by mass or more, more preferably 20% by mass or more, even more preferably 25% by mass or more, even more preferably 30% by mass or more, even more preferably 35% by mass or more, and particularly preferably 38% by mass or more, and the upper limit is preferably 80% by mass or less, more preferably 70% by mass or less, even more preferably 60% by mass or less, even more preferably 55% by mass or less, and particularly preferably 50% by mass or less. The content of the maleimide resin (A) in the resin composition is preferably 1% by mass or more, more preferably 3% by mass or more, even more preferably 5% by mass or more, even more preferably 8% by mass or more, and particularly preferably 10% by mass or more, and the upper limit is preferably 40% by mass or less, more preferably 35% by mass or less, even more preferably 30% by mass or less, even more preferably 25% by mass or less, and particularly preferably 22% by mass or less.
[0072] <(B) Anionic Polymerizable Curing Agent> The resin composition of the present invention contains an anionic polymerizable curing agent (B). The anionic polymerizable curing agent (B) can have a function of curing the maleimide resin, epoxy resin, etc. by anionically reacting with them. The anionic polymerizable curing agent (B) may be used alone or in any combination of two or more kinds.
[0073] Examples of the anionic polymerizable curing agent (B) include a phenol-based curing agent, a carbodiimide-based curing agent, an amine-based curing agent, a benzoxazine-based curing agent, an active ester-based curing agent, etc. Among these, the anionic polymerizable curing agent (B) preferably contains a phenol-based curing agent.
[0074] As the phenol-based curing agent, a curing agent having one or more, preferably two or more, hydroxyl groups (phenolic hydroxyl groups) bonded to an aromatic ring such as a benzene ring or a naphthalene ring in one molecule can be used. Examples of the phenol-based curing agent include a phenol-based curing agent having a polyphenylene ether structure, a phenol-based curing agent having a biphenyl structure (particularly preferably containing a 1-propenyl group), and a phenol-based curing agent having a novolac structure (particularly preferably containing a triazine skeleton). These may be used alone or in combination of two or more.
[0075] Examples of commercially available phenol-based curing agents include "MEH-7700", "MEH-7810", and "MEH-7851" manufactured by Meiwa Kasei Co., Ltd.; "NHN", "CBN", and "GPH" manufactured by Nippon Kayaku Co., Ltd.; "SN-170", "SN-180", "SN-190", "SN-475", "SN-485", "SN-495", "SN-375", and "SN-395" manufactured by Nippon Steel Chemical & Material Co., Ltd.; "LA-7052", "LA-7054", "LA-3018", "LA-3018-50P", "LA-1356", "TD-2090", "TD-2090-60M", and "KA-1160" manufactured by DIC Corporation; and "SA90" manufactured by SABIC Corporation. These may be used alone or in combination of two or more types.
[0076] Examples of the carbodiimide-based curing agent include curing agents having one or more, preferably two or more, carbodiimide structures in one molecule, such as aliphatic biscarbodiimides, such as tetramethylene-bis(t-butylcarbodiimide) and cyclohexane bis(methylene-t-butylcarbodiimide); aromatic biscarbodiimides, such as phenylene-bis(xylylcarbodiimide); and aliphatic polycarbodiimides, such as polyhexamethylenecarbodiimide, polytrimethylhexamethylenecarbodiimide, polycyclohexylenecarbodiimide, poly(methylenebiscyclohexylenecarbodiimide), and poly(isophoronecarbodiimide). and aromatic polycarbodiimides such as poly(phenylenecarbodiimide), poly(naphthylenecarbodiimide), poly(tolylenecarbodiimide), poly(methyldiisopropylphenylenecarbodiimide), poly(triethylphenylenecarbodiimide), poly(diethylphenylenecarbodiimide), poly(triisopropylphenylenecarbodiimide), poly(diisopropylphenylenecarbodiimide), poly(xylylenecarbodiimide), poly(tetramethylxylylenecarbodiimide), poly(methylenediphenylenecarbodiimide), and poly[methylenebis(methylphenylene)carbodiimide]. These may be used alone or in combination of two or more.
[0077] Examples of commercially available carbodiimide curing agents include "Carbodilite V-02B", "Carbodilite V-03", "Carbodilite V-04K", "Carbodilite V-07", and "Carbodilite V-09" manufactured by Nisshinbo Chemical Co., Ltd.; "Stavaxol P", "Stavaxol P400", and "Hi-Kasil 510" manufactured by Rhein Chemie. These may be used alone or in combination of two or more.
[0078] The amine-based curing agent may be a curing agent having one or more, preferably two or more, amino groups in one molecule, such as aliphatic amines, polyether amines, alicyclic amines, aromatic amines, etc., and among them, aromatic amines are preferred from the viewpoint of achieving the desired effects of the present invention. The amine-based curing agent is preferably a primary amine or secondary amine, and more preferably a primary amine.
[0079] Specific examples of amine-based curing agents include 4,4'-methylenebis(2,6-dimethylaniline), 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, m-phenylenediamine, m-xylylenediamine, diethyltoluenediamine, 4,4'-diaminodiphenyl ether, 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dihydroxybenzidine, and 2,2-bis(3-amino-4-hydroxyphenyl)propane. propane, 3,3-dimethyl-5,5-diethyl-4,4-diphenylmethanediamine, 2,2-bis(4-aminophenyl)propane, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis(4-(4-aminophenoxy)phenyl)sulfone, bis(4-(3-aminophenoxy)phenyl)sulfone, and the like. The amine-based curing agent may be a commercially available product, for example, "SEIKACURE-S" manufactured by Seika Corporation; "KAYABOND C-200S", "KAYABOND C-100", "KAYAHARD AA", "KAYAHARD AB", and "KAYAHARD AS" manufactured by Nippon Kayaku Co., Ltd.; "Epicure W" manufactured by Mitsubishi Chemical Corporation; "DTDA" manufactured by Sumitomo Seika Chemicals; and "WA" manufactured by DIC Corporation. These may be used alone or in combination of two or more types.
[0080] The benzoxazine-based curing agent includes a curing agent having one or more, preferably two or more, benzoxazine structures in one molecule.
[0081] Commercially available benzoxazine curing agents include "JBZ-OP100D" and "ODA-BOZ" manufactured by JFE Chemical Corporation, "HFB2006M" manufactured by Showa Polymer Co., Ltd., and "Pd", "Fa", and "ALP-d" manufactured by Shikoku Chemical Industry Co., Ltd. These may be used alone or in combination of two or more types.
[0082] As the active ester curing agent, generally, compounds having two or more highly reactive ester groups in one molecule, such as phenol esters, thiophenol esters, N-hydroxyamine esters, and esters of heterocyclic hydroxy compounds, are preferably used. The active ester compound is preferably one obtained by a condensation reaction between a carboxylic acid compound and / or a thiocarboxylic acid compound and a hydroxy compound and / or a thiol compound. In particular, from the viewpoint of improving heat resistance, an active ester compound obtained from a carboxylic acid compound and a hydroxy compound is preferred, and an active ester compound obtained from a carboxylic acid compound and a phenol compound and / or a naphthol compound is more preferred. Examples of the carboxylic acid compound include benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, and pyromellitic acid. Examples of phenol compounds or naphthol compounds include hydroquinone, resorcin, bisphenol A, bisphenol F, bisphenol S, phenolphthaline, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucin, benzenetriol, dicyclopentadiene-type diphenol compounds, phenol novolac, etc. Here, the term "dicyclopentadiene-type diphenol compounds" refers to diphenol compounds obtained by condensing one molecule of dicyclopentadiene with two molecules of phenol.
[0083] As the active ester curing agent, specifically, a dicyclopentadiene type active ester compound, a naphthalene type active ester compound containing a naphthalene structure, an active ester compound containing an acetylated product of a phenol novolac resin, and an active ester compound containing a benzoylated product of a phenol novolac resin are preferable, and among them, at least one selected from a dicyclopentadiene type active ester compound and a naphthalene type active ester compound is more preferable. As the dicyclopentadiene type active ester compound, an active ester compound containing a dicyclopentadiene type diphenol structure is preferable.
[0084] Commercially available active ester curing agents include active ester compounds containing a dicyclopentadiene-type diphenol structure, such as "EXB9451", "EXB9460", "EXB9460S", "HPC-8000L-65TM", "HPC-8000-65T", "HPC-8000H", and "HPC-8000H-65TM" (manufactured by DIC Corporation); and active ester compounds containing a naphthalene structure, such as "HP-B-8151-62T", "EXB-8100L-65T", "EXB-9416-70BK", "HPC-8150-62T", and "EXB-9416-70BK". B-8 (manufactured by DIC Corporation); an active ester compound containing phosphorus, "EXB9401" (manufactured by DIC Corporation), an active ester compound which is an acetylated product of phenol novolac resin, "DC808" (manufactured by Mitsubishi Chemical Corporation), active ester compounds which are benzoylated products of phenol novolac resin, "YLH1026", "YLH1030", and "YLH1048" (manufactured by Mitsubishi Chemical Corporation), and an active ester compound containing a vinylphenyl group and a naphthalene structure, "PC1300-02-65MA" (manufactured by Air Water Inc.), etc.
[0085] The reactive group equivalent of the anionic polymerizable curing agent (B) is preferably 3,000 g / eq. or less, more preferably 2,000 g / eq. or less, even more preferably 1,000 g / eq. or less, particularly preferably 800 g / eq. or less, and the lower limit is preferably 40 g / eq. or more, more preferably 60 g / eq. or more, even more preferably 80 g / eq. or more, particularly preferably 100 g / eq. or more. The reactive group equivalent is the mass of the anionic polymerizable curing agent (B) per 1 molar equivalent of reactive group. The reactive group means a functional group that reacts anionically with maleimide resin, epoxy resin, etc., for example, a phenolic hydroxyl group in the case of a phenolic curing agent, a carbodiimide group (-N=C=N-) in the case of a carbodiimide curing agent, an amino group in the case of an amine curing agent, a benzoxazinyl group in the case of a benzoxazine curing agent, and a reactive ester group (ester of a phenolic hydroxyl group) in the case of an active ester curing agent.
[0086] The content of the anionic polymerizable curing agent (B) in the resin composition is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, even more preferably 0.5% by mass or more, still more preferably 1% by mass or more, and particularly preferably 3% by mass or more, when the non-volatile components excluding the inorganic filler (D) in the resin composition are taken as 100% by mass, and the upper limit is preferably 60% by mass or less, more preferably 50% by mass or less, even more preferably 40% by mass or less, still more preferably 30% by mass or less, still more preferably 25% by mass or less, and particularly preferably 20% by mass or less. When the total non-volatile components in the resin composition is taken as 100 mass%, the content of the anionic polymerizable curing agent (B) is preferably 0.01 mass% or more, more preferably 0.05 mass% or more, even more preferably 0.1 mass% or more, still more preferably 0.15 mass% or more, and particularly preferably 0.2 mass% or more, and the upper limit is preferably 30 mass% or less, more preferably 20 mass% or less, even more preferably 15 mass% or less, still more preferably 10 mass% or less, and particularly preferably 8 mass% or less.
[0087] The mass ratio of the anionic polymerizable curing agent (B) to the maleimide resin (A) in the resin composition (the content of component (B) / the content of component (A)) is preferably 0.02 or more, more preferably 0.05 or more, even more preferably 0.07 or more, and particularly preferably 0.08 or more, and the upper limit thereof is preferably 2 or less, more preferably 1 or less, even more preferably 0.8 or less, and particularly preferably 0.6 or less.
[0088] In the resin composition, the maleimide group of the maleimide resin (A) relative to 1 molar equivalent of the reactive group of the anionic polymerizable curing agent (B) is 0.1 molar equivalent or more, preferably 0.3 molar equivalent or more, more preferably 0.5 molar equivalent or more, even more preferably 0.6 molar equivalent or more, and particularly preferably 0.7 molar equivalent or more, and the upper limit is 100 molar equivalents or less, preferably 80 molar equivalents or less, more preferably 60 molar equivalents or less, even more preferably 50 molar equivalents or less, still more preferably 40 molar equivalents or less, still more preferably 30 molar equivalents or less, and particularly preferably 20 molar equivalents or less. The reactive group refers to a functional group that reacts anionically with maleimide resins, epoxy resins, etc., and for example, refers to a phenolic hydroxyl group in a phenol-based curing agent, a carbodiimide group (-N=C=N-) in a carbodiimide-based curing agent, an amino group in an amine-based curing agent, a benzoxazinyl group in a benzoxazine-based curing agent, and a reactive ester group (ester of a phenolic hydroxyl group) in an active ester-based curing agent.
[0089] <(C) Imidazole-based curing catalyst> The resin composition of the present invention contains (C) an imidazole-based curing catalyst. The (C) imidazole-based curing catalyst functions as a catalyst that accelerates the curing of maleimide resins, epoxy resins, etc. The (C) imidazole-based curing catalyst may be used alone or in combination of two or more.
[0090] (C) The imidazole curing catalyst is represented by the formula (C):
[0091] [ka]
[0092] [In the formula, R 1 , R 3 and R 4 are each independently a hydrogen atom, -CN, or -NO 2 , -OH, -NH 2 , -CHO, -R a , -OR a , -NHR a , -NR a 2 , -COR a , -COOR a , -OCOR a , -CONHR a , -NHCOR a , -SR a , or -SO 2 R a indicates; R 2 is a hydrogen atom or -R a indicates; R 1 and R 2 , or R 2 and R 3 may be bonded together to form an optionally substituted nitrogen-containing heterocycle; R 3 and R 4 may be bonded together to form an aromatic ring which may have a substituent; R a each independently represents a monovalent hydrocarbon group which may have a substituent. The compound represented by the formula (I) is preferably a compound represented by the formula (I), a salt thereof, an isocyanuric acid adduct thereof, or an adduct thereof with an epoxy resin. Examples of the salt include carboxylates, and specifically, trimellitates.
[0093] R 1 and R 2 , or R 2 and R 3 "Optionally substituted nitrogen-containing heterocycle" formed by R 3and R 4 The "substituent" in the "optionally substituted aromatic ring" formed by is not particularly limited, but examples thereof include -NO 2 , -CN, -COH, -OH, -SH, -NH 2 , -COOH, -R, -COR, -OR, -SR, -SOR, -SO 2 R, -NHR, -NR 2 , -COOR, -OCOR, -CONH 2 , -CONHR, -CONR 2 , -NHCOR, and the like (wherein each R is independently a monovalent hydrocarbon group).
[0094] The "substituent" in the "monovalent hydrocarbon group which may be substituted" of R is not particularly limited, but examples thereof include -NO 2 , -CN, -COH, -OH, -SH, -NH 2 , -COOH, -R'', -COR', -OR', -SR', -SOR', -SO 2 R', -NHR', -N(R') 2 , -COOR', -OCOR', -CONH 2 , -CONHR', -CON(R') 2 , -NHCOR', -NHCONHR', etc. (wherein R' is independently (1) -NO 2 , -CN, -COH, -OH, -SH, -NH 2 an alkyl group which may be substituted with a group selected from the group consisting of an aryl group and an alkylaryl group; 2 , -CN, -COH, -OH, -SH, -NH 2 (3) an alkenyl group which may be substituted with a group selected from the group consisting of -NO 2 , -CN, -COH, -OH, -SH, -NH 2 an aryl group optionally substituted with a group selected from the group consisting of an alkyl group, an alkenyl group, an aryl group, an aralkyl group, and an alkylaryl group; or (4) -NO 2 , -CN, -COH, -OH, -SH, -NH 2R" represents a heteroaryl group optionally substituted with a group selected from the group consisting of an alkyl group, an alkenyl group, an aryl group, an aralkyl group, and an alkylaryl group; R" represents -NO 2 , -CN, -COH, -OH, -SH, -NH 2 , a heteroaryl group which may be substituted with a group selected from an alkyl group, an alkenyl group, an aryl group, an aralkyl group, and an alkylaryl group.
[0095] The heteroaryl group means a monovalent group obtained by removing one hydrogen atom from an aromatic heterocycle having heteroatoms such as oxygen, nitrogen, and sulfur atoms in addition to carbon atoms as ring-constituting atoms. Unless otherwise specified, the heteroaryl group is preferably a 5- to 14-membered heteroaryl group, and more preferably a 5- to 10-membered heteroaryl group. Examples of the heteroaryl group include a furyl group, a thienyl group, a pyrrolyl group, a pyrazolyl group, an oxazolyl group, an isoxazolyl group, a thiazolyl group, an imidazolyl group, a pyridyl group, a pyridazinyl group, a pyrimidinyl group, a pyrazinyl group, and a triazinyl group (e.g., 1,3,5-triazin-2-yl, etc.).
[0096] The nitrogen-containing heterocycle means a heterocycle having at least carbon and nitrogen atoms as ring-constituting atoms, and may further have heteroatoms other than nitrogen atoms, such as oxygen and sulfur atoms, as ring-constituting atoms. The nitrogen-containing heterocycle may be a monocyclic nitrogen-containing heterocycle, a bicyclic nitrogen-containing heterocycle, or a tricyclic nitrogen-containing heterocycle, but in one embodiment, a monocyclic nitrogen-containing heterocycle is preferred. In one embodiment, the nitrogen-containing heterocycle is preferably 4-14-membered, and more preferably 5-10-membered. Specific examples of suitable nitrogen-containing heterocycles include monocyclic nitrogen-containing non-aromatic heterocycles such as a pyrrolidine ring, an imidazolidine ring, an imidazoline ring, a pyrazolidine ring, a pyrazoline ring, an oxazolidine ring, an oxazoline ring, a thiazolidine ring, and a thiazoline ring; and bicyclic nitrogen-containing non-aromatic heterocycles such as an indoline ring and a dihydrobenzimidazole ring.
[0097] Specific examples of the (C) imidazole-based curing catalyst include, for example, 2-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1-methyl-2-ethylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1-isobutyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole (for example, "Curezol 2P4MZ" manufactured by Shikoku Chemical Industry Co., Ltd.), 1-benzyl-2-methylimidazole, 1-benzyl-2-ethylimidazole, 1-benzyl- 2-Phenylimidazole, 1-(2-cyanoethyl)-2-methylimidazole (e.g., Shikoku Chemical Industry Corporation's "Curezol 2MZ-CN"), 1-(2-cyanoethyl)-2-ethyl-4-methylimidazole (e.g., Shikoku Chemical Industry Corporation's "Curezol 2E4MZ-CN"), 1-(2-cyanoethyl)-2-undecylimidazole (e.g., Shikoku Chemical Industry Corporation's "Curezol C11Z-CN"), 1-(2-cyanoethyl)-2-undecylimidazole trimellitate, 1-(2-cyanoethyl)-2-phenylimidazole (e.g., For example, Shikoku Chemical Industry Co., Ltd.'s "Curezol 2PZ-CN"), 1-aminoethyl-2-methylimidazole, 1-(cyanoethylaminoethyl)-2-methylimidazole, 1-(2-cyanoethyl)-2-methylimidazole trimellitate (for example, Shikoku Chemical Industry Co., Ltd.'s "Curezol 2MZ-CNS"), 1-(2-cyanoethyl)-2-ethyl-4-methylimidazole trimellitate (for example, Shikoku Chemical Industry Co., Ltd.'s "Curezol 2E4MZ-CNS"), 1-(2-cyanoethyl)-2-undecylimidazole trimellitate (for example, For example, Shikoku Chemical Industry Corporation's "Curezol C11Z-CNS"), 1-(2-cyanoethyl)-2-phenylimidazole trimellitate (for example, Shikoku Chemical Industry Corporation's "Curezol 2PZ-CNS"), 1-benzyl-2-phenylimidazole (for example, Shikoku Chemical Industry Corporation's "Curezol 1B2PZ"), 1-benzyl-2-phenylimidazole trimellitate (for example, Shikoku Chemical Industry Corporation's "Curezol 1B2PZ-S"), 2,4-diamino-6-(2-ethyl-4-methyl-1-imidazolyl)ethyl-1,3,5-triazine, 2,4-diamino-6-(2-methyl-1-imidazolyl)ethyl-1,3,5-triazine (e.g., Shikoku Chemical Industry Co., Ltd.'s "Curezol 2MZ-A" and "Curezol 2MZA-PW"), 2,4-diamino-6-(2-undecyl-1-imidazolyl)ethyl-1,3,5-triazine (e.g., Shikoku Chemical Industry Co., Ltd.'s "Curezol C11Z-A"), 2,4-diamino-6-(2-ethyl-4-methyl-1-imidazolyl)ethyl-1,3,5-triazine (e.g., Shikoku Chemical Industry Co., Ltd.'s "Curezol 2E4MZ-A"), 2-methyl- Imidazole-isocyanuric acid adduct (e.g., Shikoku Chemical Industry Co., Ltd.'s "Curezol 2MZ-OK"), 2-phenylimidazole-isocyanuric acid adduct (e.g., Shikoku Chemical Industry Co., Ltd.'s "Curezol 2PZ-OK"), 2,4-diamino-6-(2-methyl-1-imidazolyl)ethyl-1,3,5-triazine-isocyanuric acid adduct (e.g., Shikoku Chemical Industry Co., Ltd.'s "Curezol 2MA-OK"), 4-formylimidazole, 2-phenyl-4-formylimidazole, 4,4'-bis(2-ethyl-5-methylimidazolyl)methan 2-phenyl-4-methyl-5-hydroxymethylimidazole (e.g., Shikoku Chemical Industry Corporation's "Curezol 2E4MZ·BIZ"), 2-phenyl-4,5-bis(hydroxymethyl)imidazole (e.g., Shikoku Chemical Industry Corporation's "Curezol 2P4MHZ"), 2-phenyl-4,5-bis(hydroxymethyl)imidazole (e.g., Shikoku Chemical Industry Corporation's "Curezol 2PHZ", "Curezol 2PHZ-PW"), 1-cyanoethyl-2-phenyl-4,5-bis(cyanoethoxymethyl)imidazole (e.g., Shikoku Chemical Industry Corporation's "Curezol 2PHZ-CN"), 1-dodecyl-2 Examples of imidazole compounds include imidazole compounds such as N,N'-(2-methyl-1-imidazolylethyl)adipamide, 1,3-dibenzyl-2-methylimidazole, 4,5-bis(hydroxymethyl)-2-phenylimidazole, and 2-phenyl-4-methyl-5-hydroxymethylimidazole, and may also be adducts of imidazole compounds and epoxy resins (for example, "Cureduct P-0505" manufactured by Shikoku Chemical Industry Co., Ltd., "JER Cure P200H50" manufactured by Mitsubishi Chemical Corporation, etc.).
[0098] The molecular weight of the (C) imidazole-based curing catalyst is preferably 2,000 or less, more preferably 1,000 or less, even more preferably 700 or less, even more preferably 500 or less, and particularly preferably 400 or less. The lower limit is not particularly limited, but may be, for example, 80 or more, 100 or more, etc.
[0099] The melting point of the (C) imidazole-based curing catalyst is preferably 120°C or higher, more preferably 140°C or higher, even more preferably 160°C or higher, and particularly preferably 180°C or higher, and the upper limit is preferably 245°C or lower, more preferably 220°C or lower, even more preferably 210°C or lower, and particularly preferably 200°C or lower.
[0100] The content of the (C) imidazole-based curing catalyst in the resin composition is preferably 0.001% by mass or more, more preferably 0.01% by mass or more, even more preferably 0.1% by mass or more, still more preferably 0.5% by mass or more, and particularly preferably 1% by mass or more, when the non-volatile components excluding the (D) inorganic filler in the resin composition is taken as 100% by mass, and the upper limit is preferably 20% by mass or less, more preferably 15% by mass or less, even more preferably 10% by mass or less, still more preferably 7% by mass or less, and particularly preferably 5% by mass or less. When the total non-volatile components in the resin composition is taken as 100% by mass, the content of the imidazole curing catalyst (C) is preferably 0.001% by mass or more, more preferably 0.01% by mass or more, even more preferably 0.05% by mass or more, still more preferably 0.1% by mass or more, and particularly preferably 0.3% by mass or more, and the upper limit is preferably 10% by mass or less, more preferably 5% by mass or less, even more preferably 3% by mass or less, still more preferably 2% by mass or less, and particularly preferably 1.5% by mass or less.
[0101] The mass ratio of the imidazole curing catalyst (C) to the maleimide resin (A) in the resin composition (the content of component (C) / the content of component (A)) is preferably 0.005 or more, more preferably 0.01 or more, even more preferably 0.02 or more, and particularly preferably 0.03 or more, and the upper limit thereof is preferably 0.5 or less, more preferably 0.3 or less, even more preferably 0.2 or less, and particularly preferably 0.15 or less.
[0102] <(D) Inorganic filler> The resin composition of the present invention contains an inorganic filler (D). The inorganic filler (D) is contained in the resin composition in the form of particles.
[0103] (D) An inorganic compound is used as the material of the inorganic filler. (D) Examples of the material of the inorganic filler include silica, alumina, aluminosilicate, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate titanate, barium zirconate, calcium zirconate, zirconium phosphate, and zirconium tungstate phosphate. Among these, silica, alumina, or aluminosilicate is preferred, and silica is particularly preferred. Examples of silica include amorphous silica, fused silica, crystalline silica, synthetic silica, and hollow silica. In addition, spherical silica is preferred as the silica. The (D) inorganic filler may be used alone or in combination of two or more kinds in any ratio.
[0104] (D) Examples of commercially available inorganic fillers include "SP60-05" and "SP507-05" manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YC100C", "YA050C", "YA050C-MJE", "YA010C", "SC2500SQ", "SO-C4", "SO-C2", and "SO-C1" manufactured by Admatechs Co., Ltd.; "UFP-30", "DAW-03", and "FB-105FD" manufactured by Denka Co., Ltd.; "Silfil NSS-3N", "Silfil NSS-4N", and "Silfil NSS-5N" manufactured by Tokuyama Corporation; "Cellspheres" and "MGH-005" manufactured by Pacific Cement Corporation; "Spherique" and "BA-1" manufactured by JGC Catalysts and Chemicals Co., Ltd.; and "Hipressica FH" manufactured by Ube Exsymo Co., Ltd.
[0105] The average particle size of the (D) inorganic filler is not particularly limited, but is preferably 10 μm or less, more preferably 5 μm or less, even more preferably 3 μm or less, even more preferably 1 μm or less, and particularly preferably 0.8 μm or less. The lower limit of the average particle size of the (D) inorganic filler is not particularly limited, but is preferably 0.01 μm or more, more preferably 0.05 μm or more, even more preferably 0.1 μm or more, and particularly preferably 0.2 μm or more. The average particle size of the (D) inorganic filler can be measured by a laser diffraction / scattering method based on the Mie scattering theory. Specifically, the particle size distribution of the inorganic filler is created on a volume basis using a laser diffraction / scattering particle size distribution measuring device, and the median diameter is taken as the average particle size. The measurement sample can be prepared by weighing 100 mg of the inorganic filler and 10 g of methyl ethyl ketone into a vial and dispersing it by ultrasonic waves for 10 minutes. The measurement sample was measured using a laser diffraction type particle size distribution measuring device with blue and red light source wavelengths, and the particle size distribution of the inorganic filler on a volume basis was measured using a flow cell method, and the average particle size was calculated as the median diameter from the particle size distribution obtained. An example of a laser diffraction type particle size distribution measuring device is the "LA-960" manufactured by Horiba, Ltd.
[0106] The specific surface area of the (D) inorganic filler is not particularly limited, but is preferably 0.1 m 2 / g or more, more preferably 0.5m 2 / g or more, more preferably 1m 2 / g or more, particularly preferably 3m 2 The upper limit of the specific surface area of the inorganic filler (D) is not particularly limited, but is preferably 100 m 2 / g or less, more preferably 50m 2 / g or less, more preferably 30m 2 / g or less, particularly preferably 10m 2 The specific surface area of the inorganic filler is obtained by adsorbing nitrogen gas onto the surface of a sample using a specific surface area measuring device (Macsorb HM-1210 manufactured by Mountech Co., Ltd.) according to the BET method, and calculating the specific surface area using the BET multipoint method.
[0107] The (D) inorganic filler may be a solid inorganic filler having an average porosity of 0 volume % (preferably solid silica, solid alumina, solid aluminosilicate), or may be a hollow inorganic filler having an average porosity of more than 0 volume % (preferably hollow silica, hollow alumina, hollow aluminosilicate).
[0108] The average porosity of the hollow inorganic filler is preferably 90% by volume or less, more preferably 80% by volume or less. The lower limit of the average porosity of the hollow inorganic filler is not particularly limited, but is, for example, more than 0% by volume, 1% by volume or more, preferably 5% by volume or more, more preferably 10% by volume or more, and even more preferably 15% by volume or more. The average porosity P (volume %) of the inorganic filler is defined as the volume-based ratio of the total volume of one or more voids present inside the particle to the total volume of the particle based on the outer surface of the particle (total volume of voids / volume of particle), and is, for example, the measured value D of the actual density of the inorganic filler. M (g / cm 3 ), and the theoretical value of the material density of the material forming the inorganic filler D T (g / cm 3 ) is used to calculate according to the following formula (I).
[0109]
number
[0110] The actual density of the inorganic filler can be measured, for example, by using a true density measuring device. Examples of the true density measuring device include ULTRAPYCNOMETER 1000 manufactured by QUANTACHROME Co., Ltd. As the measurement gas, for example, nitrogen is used.
[0111] (D) The inorganic filler is preferably treated with a surface treatment agent from the viewpoint of improving moisture resistance and dispersibility. Examples of the surface treatment agent include fluorine-containing silane coupling agents, aminosilane coupling agents, epoxysilane coupling agents, mercaptosilane coupling agents, silane coupling agents, alkoxysilanes, organosilazane compounds, titanate coupling agents, etc. The surface treatment agent may be used alone or in any combination of two or more.
[0112] Examples of commercially available surface treatment agents include Shin-Etsu Chemical Co., Ltd.'s "KBM403" (3-glycidoxypropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM803" (3-mercaptopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBE903" (3-aminopropyltriethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM573" (N-phenyl-3-aminopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "SZ-31" (hexamethyldisilazane), Shin-Etsu Chemical Co., Ltd.'s "KBM103" (phenyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM-4803" (long-chain epoxy-type silane coupling agent), and Shin-Etsu Chemical Co., Ltd.'s "KBM-7103" (3,3,3-trifluoropropyltrimethoxysilane).
[0113] From the viewpoint of improving the dispersibility of the inorganic filler, the degree of surface treatment with the surface treatment agent is preferably within a predetermined range. Specifically, 100% by mass of the inorganic filler is preferably surface-treated with 0.2% to 5% by mass of the surface treatment agent, more preferably 0.2% to 3% by mass, and even more preferably 0.3% to 2% by mass.
[0114] The degree of surface treatment with the surface treatment agent can be evaluated by the amount of carbon per unit surface area of the inorganic filler. From the viewpoint of improving the dispersibility of the inorganic filler, the amount of carbon per unit surface area of the inorganic filler is set to 0.02 mg / m 2 More than 0.1 mg / m is preferable. 2 More preferably, 0.2 mg / m or more 2 On the other hand, from the viewpoint of preventing an increase in the melt viscosity of the resin composition or the melt viscosity in the form of a sheet, it is more preferable that the melt viscosity is 1.0 mg / m 2 Less than 0.8 mg / m is preferred. 2 Less than 0.5 mg / m is more preferable. 2 The following is even more preferred:
[0115] (D) The amount of carbon per unit surface area of the inorganic filler can be measured after the surface-treated inorganic filler is washed with a solvent (e.g., methyl ethyl ketone (MEK)). Specifically, a sufficient amount of MEK as a solvent is added to the inorganic filler that has been surface-treated with a surface treatment agent, and ultrasonic cleaning is performed at 25°C for 5 minutes. After removing the supernatant and drying the solid content, the amount of carbon per unit surface area of the inorganic filler can be measured using a carbon analyzer. As the carbon analyzer, the "EMIA-320V" manufactured by Horiba, Ltd., or the like can be used.
[0116] The content of the (D) inorganic filler in the resin composition is 50% by mass or more, preferably 55% by mass or more, more preferably 60% by mass or more, even more preferably 65% by mass or more, still more preferably 70% by mass or more, and particularly preferably 72% by mass or more, and the upper limit thereof is preferably 90% by mass or less, more preferably 85% by mass or less, even more preferably 80% by mass or less, and particularly preferably 75% by mass or less, when the total non-volatile components in the resin composition is 100% by mass.
[0117] The mass ratio of the inorganic filler (D) to the maleimide resin (A) in the resin composition (component (D) / component (A)) is not particularly limited, but is preferably 1.5 or more, more preferably 2 or more, even more preferably 2.3 or more, and particularly preferably 2.5 or more, and the upper limit is preferably 25 or less, more preferably 20 or less, even more preferably 15 or less, even more preferably 10 or less, and particularly preferably 8 or less.
[0118] The total content of the (A) maleimide resin, (B) anionic polymerizable curing agent, (C) imidazole-based curing catalyst, and (D) inorganic filler in the resin composition is preferably 60 mass% or more, more preferably 70 mass% or more, even more preferably 75 mass% or more, still more preferably 78 mass% or more, and particularly preferably 80 mass% or more, based on 100 mass% of all non-volatile components in the resin composition.
[0119] <(E) Epoxy resin> The resin composition of the present invention may contain an epoxy resin (E) in an amount of 0 to 1% by mass relative to 100% by mass of the non-volatile components excluding the inorganic filler (D). The epoxy resin (E) is a curable resin having an epoxy group and an epoxy equivalent of 5,000 g / eq. or less.
[0120] Examples of the (E) epoxy resin include bixylenol type epoxy resins, bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, bisphenol AF type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, naphthol novolac type epoxy resins, phenol novolac type epoxy resins, tert-butyl-catechol type epoxy resins, naphthalene type epoxy resins, naphthol type epoxy resins, anthracene type epoxy resins, glycidylamine type epoxy resins, glycidyl ester type epoxy resins, cresol novolac type epoxy resins, phenol aralkyl type epoxy resins, biphenyl type epoxy resins, linear aliphatic epoxy resins, epoxy resins having a butadiene structure, alicyclic epoxy resins, heterocyclic epoxy resins, spiro ring-containing epoxy resins, cyclohexane type epoxy resins, cyclohexane dimethanol type epoxy resins, naphthylene ether type epoxy resins, trimethylol type epoxy resins, tetraphenylethane type epoxy resins, isocyanurate type epoxy resins, and phenolphthalimidine type epoxy resins. The (E) epoxy resin may be used alone or in combination of two or more kinds.
[0121] The resin composition of the present invention preferably contains, as the epoxy resin (E), an epoxy resin having two or more epoxy groups in one molecule. The proportion of the epoxy resin having two or more epoxy groups in one molecule relative to 100% by mass of the epoxy resin (E) is preferably 50% by mass or more, more preferably 60% by mass or more, and particularly preferably 70% by mass or more.
[0122] (E) Epoxy resins include epoxy resins that are liquid at a temperature of 20° C. (hereinafter sometimes referred to as "liquid epoxy resins") and epoxy resins that are solid at a temperature of 20° C. (hereinafter sometimes referred to as "solid epoxy resins"). The resin composition of the present invention may contain only liquid epoxy resins as epoxy resins, or only solid epoxy resins, or both liquid and solid epoxy resins, but it is particularly preferable that the resin composition contains both liquid and solid epoxy resins.
[0123] The liquid epoxy resin is preferably a liquid epoxy resin having two or more epoxy groups in one molecule.
[0124] As the liquid epoxy resin, glycirol type epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AF type epoxy resin, naphthalene type epoxy resin, glycidyl ester type epoxy resin, glycidyl amine type epoxy resin, phenol novolac type epoxy resin, alicyclic epoxy resin having an ester skeleton, cyclohexane dimethanol type epoxy resin, cyclic aliphatic glycidyl ether, and epoxy resin having a butadiene structure are preferred.
[0125] Specific examples of liquid epoxy resins include "EX-992L" manufactured by Nagase ChemteX Corporation, "YX7400" manufactured by Mitsubishi Chemical Corporation, "HP4032", "HP4032D", and "HP4032SS" (naphthalene type epoxy resins) manufactured by DIC Corporation; "828US", "jER828EL", "828EL", "825", and "Epikote 828EL" (bisphenol A type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER807" and "1750" ( bisphenol F type epoxy resin; "jER152" (phenol novolac type epoxy resin) manufactured by Mitsubishi Chemical; "630", "630LSD", "604" (glycidylamine type epoxy resin) manufactured by Mitsubishi Chemical; "ED-523T" (glycirol type epoxy resin) manufactured by ADEKA; "EP-3950L", "EP-3980S" (glycidylamine type epoxy resin) manufactured by ADEKA; "EP-4088S" (dicyclopentadiene type epoxy resin) manufactured by ADEKA; "ZX1059" (mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin) manufactured by Nippon Steel Chemical & Material; "EX-721" (glycidyl ester type epoxy resin) manufactured by Nagase ChemteX; "EX-991L" (alkyleneoxy and butadiene type epoxy resin) manufactured by Nagase ChemteX; "Celloxide 2021P" (alicyclic epoxy resin with ester structure) manufactured by Daicel ); "PB-3600" manufactured by Daicel Corporation, "JP-100" and "JP-200" manufactured by Nippon Soda Co., Ltd. (epoxy resins having a butadiene structure); "ZX1658" and "ZX1658GS" (liquid 1,4-glycidylcyclohexane type epoxy resins) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "EG-280" (fluorene structure-containing epoxy resin) manufactured by Osaka Gas Chemicals Co., Ltd.; and "EX-201" (cyclic aliphatic glycidyl ether) manufactured by Nagase ChemteX Corporation.
[0126] As the solid epoxy resin, a solid epoxy resin having three or more epoxy groups in one molecule is preferable, and an aromatic solid epoxy resin having three or more epoxy groups in one molecule is more preferable.
[0127] Preferred solid epoxy resins include bixylenol type epoxy resins, naphthalene type epoxy resins, naphthalene type tetrafunctional epoxy resins, naphthol novolac type epoxy resins, cresol novolac type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, naphthol type epoxy resins, biphenyl type epoxy resins, naphthylene ether type epoxy resins, anthracene type epoxy resins, bisphenol A type epoxy resins, bisphenol AF type epoxy resins, phenol aralkyl type epoxy resins, tetraphenylethane type epoxy resins, and phenolphthalimidine type epoxy resins.
[0128] Specific examples of solid epoxy resins include "HP4032H" (naphthalene type epoxy resin) manufactured by DIC Corporation; "HP-4700" and "HP-4710" (naphthalene type tetrafunctional epoxy resins) manufactured by DIC Corporation; "N-690" (cresol novolac type epoxy resin) manufactured by DIC Corporation; "N-695" (cresol novolac type epoxy resin) manufactured by DIC Corporation; "HP-7200", "HP-7200HH", "HP-7200H", and "HP-7200L" (dicyclopentadiene type epoxy resins) manufactured by DIC Corporation; "EXA-7311" and "E XA-7311-G3, EXA-7311-G4, EXA-7311-G4S, HP6000, HP6000L (naphthylene ether type epoxy resin); EPPN-502H (trisphenol type epoxy resin) manufactured by Nippon Kayaku; NC7000L (naphthol novolac type epoxy resin) manufactured by Nippon Kayaku; NC3000H, NC3000, NC3000L, NC3000FH, NC3100 (biphenyl type epoxy resin) manufactured by Nippon Steel Chemical & Material; ESN475V manufactured by Nippon Steel Chemical & Material; "ESN4100V" (naphthalene type epoxy resin); "ESN485" (naphthol type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "ESN375" (dihydroxynaphthalene type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YX4000H", "YX4000", "YX4000HK", "YL7890" (bixylenol type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; "YL6121" (biphenyl type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; "YX8800" (anthracene type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd. Examples of epoxy resins include "YX7700" (phenol aralkyl type epoxy resin); "PG-100" and "CG-500" manufactured by Osaka Gas Chemicals; "YL7760" (bisphenol AF type epoxy resin) manufactured by Mitsubishi Chemical; "YL7800" (fluorene type epoxy resin) manufactured by Mitsubishi Chemical; "jER1010" (bisphenol A type epoxy resin) manufactured by Mitsubishi Chemical; "jER1031S" (tetraphenylethane type epoxy resin) manufactured by Mitsubishi Chemical; and "WHR991S" (phenolphthalimidine type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.These may be used alone or in combination of two or more.
[0129] When a liquid epoxy resin and a solid epoxy resin are used in combination as the (E) epoxy resin, the mass ratio thereof (liquid epoxy resin:solid epoxy resin) is preferably 10:1 to 1:50, more preferably 5:1 to 1:20, even more preferably 2:1 to 1:10, and particularly preferably 1:1 to 1:3.
[0130] The epoxy equivalent of the (E) epoxy resin is preferably 50 g / eq. to 5,000 g / eq., more preferably 60 g / eq. to 2,000 g / eq., even more preferably 70 g / eq. to 1,000 g / eq., and even more preferably 80 g / eq. to 500 g / eq. The epoxy equivalent is the mass of the resin per equivalent of epoxy group. This epoxy equivalent can be measured according to JIS K7236.
[0131] The weight average molecular weight (Mw) of the (E) epoxy resin is preferably from 100 to 5,000, more preferably from 250 to 3,000, and further preferably from 400 to 1500. The weight average molecular weight of the resin can be measured by gel permeation chromatography (GPC) as a polystyrene-equivalent value.
[0132] The content of the (E) epoxy resin in the resin composition is 0% by mass to 1% by mass, assuming that the non-volatile components excluding the (D) inorganic filler in the resin composition are 100% by mass, and in one embodiment, is preferably 0% by mass to 0.8% by mass, more preferably 0% by mass to 0.7% by mass, even more preferably 0% by mass to 0.5% by mass, still more preferably 0% by mass to 0.3% by mass, even more preferably 0% by mass to 0.1% by mass, even more preferably 0% by mass to 0.01% by mass, and particularly preferably 0% by mass to 0.001% by mass.
[0133] In one embodiment, it is preferable to include a specific amount of (E) epoxy resin from the viewpoint of achieving both copper adhesion strength and mechanical strength. In this embodiment, the content of (E) epoxy resin in the resin composition is preferably 0.001 mass% or more, more preferably 0.01 mass% or more, even more preferably 0.1 mass% or more, and particularly preferably 0.3 mass% or more, and its upper limit is 1 mass% or less, preferably 0.8 mass% or less, more preferably 0.7 mass% or less. If the content of epoxy resin exceeds 1 mass%, the mechanical strength decreases, and if it exceeds 5 mass%, the copper adhesion strength and mechanical strength as well as the dielectric loss tangent tend to be impaired.
[0134] <(F) Ethylenically unsaturated bond-containing resin> The resin composition of the present invention may further contain an ethylenically unsaturated bond-containing resin (F) as an optional component. The ethylenically unsaturated bond-containing resin (F) described here is a component other than the maleimide resin (A) and the anionic polymerizable curing agent (B) described above. Examples of the ethylenically unsaturated bond-containing resin (F) include polystyrene resins having ethylenically unsaturated groups and benzocyclobutene resins having ethylenically unsaturated groups.
[0135] The polystyrene resin having an ethylenically unsaturated group is preferably Formula (F1):
[0136] [ka]
[0137] [In the formula, R a1 , R a2 and R a3 each independently represents a hydrogen atom or an alkyl group; R a4 each independently represents an alkyl group; a represents an integer of 0 to 5. A repeating structural unit represented by the formula: Formula (F2):
[0138] [ka]
[0139] [In the formula, R b1 , R b2 , R b3 , R b5 , R b6 and R b7 each independently represents a hydrogen atom or an alkyl group; R b4 each independently represents an alkyl group; and b represents an integer of 0 to 4. and a polystyrene-based resin containing a repeating structural unit represented by the following formula:
[0140] The benzocyclobutene resin having an ethylenically unsaturated group is an ethylenically unsaturated group-containing compound having one or more benzocyclobutene rings, preferably two or more benzocyclobutene rings.In one embodiment, the benzocyclobutene resin having an ethylenically unsaturated group preferably further has an organosiloxane skeleton.As the organosiloxane skeleton, for example, dialkylsiloxane skeleton such as dimethylsiloxane skeleton; diarylsiloxane skeleton such as diphenylsiloxane skeleton, etc. can be mentioned, and dialkylsiloxane skeleton is preferable, and dimethylsiloxane skeleton is particularly preferable.
[0141] The benzocyclobutene resin having an ethylenically unsaturated group is preferably represented by the formula (F3):
[0142] [ka]
[0143] [In the formula, R c1 and R c3 each independently represents a hydrogen atom or a monovalent hydrocarbon group; R c2 and R c4each independently represents a monovalent hydrocarbon group; c's each independently represent an integer of 0 to 3; Each d is independently an integer of 1 or more. It is a resin represented by the formula:
[0144] R c1 and R c3 R each independently represents a hydrogen atom or a monovalent hydrocarbon group, is preferably a hydrogen atom or an alkyl group, and is particularly preferably a hydrogen atom. c2 and R c4 each independently represents a monovalent hydrocarbon group, preferably an alkyl group or an aryl group, and particularly preferably an alkyl group. each c independently represents an integer of 0 to 3, and preferably 0. each d independently represents an integer of 1 or more, preferably an integer of 1 to 3, and more preferably 1.
[0145] An example of a commercially available benzocyclobutene resin having an ethylenically unsaturated group is "CYCLOTENE 3022" manufactured by The Dow Chemical Company.
[0146] The weight average molecular weight (Mw) of the (F) ethylenically unsaturated bond-containing resin is preferably 500 or more, more preferably 1,000 or more, even more preferably 2,000 or more, and particularly preferably 3,000 or more, and the upper limit is preferably 100,000 or less, more preferably 70,000 or less, even more preferably 60,000 or less, and particularly preferably 50,000 or less.
[0147] The content of the (F) ethylenically unsaturated bond-containing resin in the resin composition, when the non-volatile components excluding the (D) inorganic filler in the resin composition is taken as 100 mass%, is, for example, 0 mass% or more, preferably 0.01 mass% or more, more preferably 0.1 mass% or more, even more preferably 1 mass% or more, still more preferably 5 mass% or more, even more preferably 10 mass% or more, and particularly preferably 15 mass% or more, and the upper limit is preferably 70 mass% or less, more preferably 60 mass% or less, even more preferably 55 mass% or less, even more preferably 50 mass% or less, and particularly preferably 45 mass% or less. When all nonvolatile components in the resin composition are taken as 100 mass%, the content of the (F) ethylenically unsaturated bond-containing resin is, for example, 0 mass% or more, preferably 0.01 mass% or more, more preferably 0.1 mass% or more, even more preferably 1 mass% or more, still more preferably 3 mass% or more, and particularly preferably 4 mass% or more; the upper limit is preferably 30 mass% or less, more preferably 25 mass% or less, even more preferably 20 mass% or less, still more preferably 15 mass% or less, and particularly preferably 10 mass% or less.
[0148] The total content of the (A) maleimide resin, (B) anionic polymerizable curing agent, (C) imidazole-based curing catalyst, (D) inorganic filler, (E) epoxy resin, and (F) ethylenically unsaturated bond-containing resin in the resin composition is preferably 80 mass% or more, more preferably 70 mass% or more, even more preferably 75 mass% or more, still more preferably 80 mass% or more, still more preferably 85 mass% or more, and particularly preferably 90 mass% or more, when the total nonvolatile components in the resin composition is 100 mass%.
[0149] <(G)Thermoplastic resin> The resin composition of the present invention may further contain a thermoplastic resin (G) as an optional component. The thermoplastic resin (G) described here is a component other than the anionic polymerizable curing agent (B) and the epoxy resin (E) described above.
[0150] Examples of the (G) thermoplastic resin include oxazoline group-containing polymers, polyimide resins, phenoxy resins, polyvinyl acetal resins, polyolefin resins, polybutadiene resins, polyamideimide resins, polyetherimide resins, polysulfone resins, polyethersulfone resins, polyphenylene ether resins, polycarbonate resins, polyetheretherketone resins, and polyester resins. In one embodiment, the (G) thermoplastic resin preferably contains a thermoplastic resin selected from the group consisting of oxazoline group-containing polymers, polyimide resins, and phenoxy resins, more preferably contains a thermoplastic resin selected from the group consisting of polyimide resins and phenoxy resins, and particularly preferably contains a phenoxy resin. The thermoplastic resin may be used alone or in combination of two or more types.
[0151] Examples of the oxazoline group-containing polymer include 2-isopropenyl-2-oxazoline, 5-methyl-2-isopropenyl-2-oxazoline, 4,4-dimethyl-2-isopropenyl-2-oxazoline, 4-methyl-2-isopropenyl-2-oxazoline, 4,4,5-trimethyl-2-isopropenyl-2-oxazoline, 2-vinyl-2-oxazoline, 5-methyl-2-vinyl-2-oxazoline, 4,4-dimethyl-2-vinyl-2-oxazoline, 4-methyl-2- It is obtained by polymerizing an addition-polymerizable oxazoline compound (vinyloxazoline skeleton-containing monomer) such as vinyl-2-oxazoline or 4,4,5-trimethyl-2-vinyl-2-oxazoline, and may be copolymerized with other monomers such as styrene-based monomers such as styrene, α-methylstyrene, 4-methylstyrene, 3-methylstyrene, 2-methylstyrene, 4-ethylstyrene, 4-tert-butylstyrene, p-divinylbenzene, m-divinylbenzene, etc. A specific example of an oxazoline group-containing polymer is "PX-3-RP-61" manufactured by Nippon Shokubai Co., Ltd.
[0152] Specific examples of polyimide resins include "SLK-6100" manufactured by Shin-Etsu Chemical Co., Ltd., and "Rikacoat SN20" and "Rikacoat PN20" manufactured by New Japan Chemical Co., Ltd.
[0153] Examples of the phenoxy resin include phenoxy resins having one or more skeletons selected from the group consisting of bisphenol A skeleton, bisphenol F skeleton, bisphenol S skeleton, bisphenolacetophenone skeleton, novolac skeleton, biphenyl skeleton, fluorene skeleton, dicyclopentadiene skeleton, norbornene skeleton, naphthalene skeleton, anthracene skeleton, adamantane skeleton, terpene skeleton, and trimethylcyclohexane skeleton. The terminal of the phenoxy resin may be any functional group such as a phenolic hydroxyl group or an epoxy group.
[0154] Specific examples of phenoxy resins include "1256" and "4250" manufactured by Mitsubishi Chemical Corporation (both of which are phenoxy resins containing a bisphenol A skeleton); "YX8100" manufactured by Mitsubishi Chemical Corporation (phenoxy resin containing a bisphenol S skeleton); "YX6954" manufactured by Mitsubishi Chemical Corporation (phenoxy resin containing a bisphenol acetophenone skeleton), "FX280" and "FX293" manufactured by Nippon Steel Chemical & Material Co., Ltd.; and "YX7200B35", "YL7500BH30", "YX6954BH30", "YX7553BH30", "YL7769BH30", "YL6794", "YL7213", "YL7290", and "YL7482" manufactured by Mitsubishi Chemical Corporation.
[0155] Examples of polyvinyl acetal resin include polyvinyl formal resin and polyvinyl butyral resin, and polyvinyl butyral resin is preferred.Specific examples of polyvinyl acetal resin include "Denka Butyral 4000-2", "Denka Butyral 5000-A", "Denka Butyral 6000-C", and "Denka Butyral 6000-EP" manufactured by Denki Kagaku Kogyo Co., Ltd.; S-LEC BH series, BX series (e.g. BX-5Z), KS series (e.g. KS-1), BL series, and BM series manufactured by Sekisui Chemical Co., Ltd.
[0156] Examples of polyolefin resins include ethylene-based copolymer resins such as low-density polyethylene, very low-density polyethylene, high-density polyethylene, ethylene-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer, and ethylene-methyl acrylate copolymer; and polyolefin polymers such as polypropylene and ethylene-propylene block copolymer.
[0157] Examples of polybutadiene resins include hydrogenated polybutadiene skeleton-containing resins, hydroxy group-containing polybutadiene resins, phenolic hydroxy group-containing polybutadiene resins, carboxy group-containing polybutadiene resins, acid anhydride group-containing polybutadiene resins, epoxy group-containing polybutadiene resins, isocyanate group-containing polybutadiene resins, urethane group-containing polybutadiene resins, polyphenylene ether-polybutadiene resins, and the like.
[0158] Specific examples of polyamide-imide resins include "Viromax HR11NN" and "Viromax HR16NN" manufactured by Toyobo Co., Ltd. Specific examples of polyamide-imide resins also include modified polyamide-imides such as "KS9100" and "KS9300" (polysiloxane skeleton-containing polyamide-imide) manufactured by Hitachi Chemical Co., Ltd.
[0159] A specific example of the polyethersulfone resin is "PES5003P" manufactured by Sumitomo Chemical Co., Ltd.
[0160] Specific examples of polysulfone resins include polysulfones "P1700" and "P3500" manufactured by Solvay Advanced Polymers.
[0161] A specific example of the polyphenylene ether resin is NORYL SA90 manufactured by SABIC, etc. A specific example of the polyetherimide resin is ULTEM manufactured by GE, etc.
[0162] Examples of polycarbonate resins include hydroxyl group-containing carbonate resins, phenolic hydroxyl group-containing carbonate resins, carboxyl group-containing carbonate resins, acid anhydride group-containing carbonate resins, isocyanate group-containing carbonate resins, and urethane group-containing carbonate resins. Specific examples of polycarbonate resins include Mitsubishi Gas Chemical's "FPC0220," Asahi Kasei Chemical's "T6002" and "T6001" (polycarbonate diols), and Kuraray's "C-1090," "C-2090," and "C-3090" (polycarbonate diols). Specific examples of polyether ether ketone resins include Sumitomo Chemical's "Sumiploy K."
[0163] Examples of the polyester resin include polyethylene terephthalate resin, polyethylene naphthalate resin, polybutylene terephthalate resin, polybutylene naphthalate resin, polytrimethylene terephthalate resin, polytrimethylene naphthalate resin, and polycyclohexane dimethyl terephthalate resin.
[0164] The weight average molecular weight (Mw) of the thermoplastic resin (G) is, from the viewpoint of significantly obtaining the effects of the present invention, preferably 5,000 or more, more preferably 8,000 or more, even more preferably 10,000 or more, particularly preferably 20,000 or more, and is preferably 100,000 or less, more preferably 70,000 or less, even more preferably 60,000 or less, particularly preferably 50,000 or less.
[0165] The content of the (G) thermoplastic resin in the resin composition, when the non-volatile components excluding the (D) inorganic filler in the resin composition is taken as 100 mass%, is, for example, 0 mass% or more, preferably 0.01 mass% or more, more preferably 0.1 mass% or more, even more preferably 0.5 mass% or more, even more preferably 1 mass% or more, still more preferably 2 mass% or more, particularly preferably 3 mass% or more, and particularly preferably 4 mass% or more, and the upper limit is preferably 70 mass% or less, more preferably 60 mass% or less, even more preferably 50 mass% or less, even more preferably 40 mass% or less, and particularly preferably 35 mass% or less. When all nonvolatile components in the resin composition are taken as 100 mass%, the content of the (G) thermoplastic resin is, for example, 0 mass% or more, preferably 0.01 mass% or more, more preferably 0.1 mass% or more, even more preferably 0.5 mass% or more, still more preferably 1 mass% or more, and particularly preferably 1.3 mass% or more; the upper limit is preferably 35 mass% or less, more preferably 30 mass% or less, even more preferably 25 mass% or less, still more preferably 20 mass% or less, and particularly preferably 15 mass% or less.
[0166] The total content of the (A) maleimide resin, (B) anionic polymerizable curing agent, (C) imidazole-based curing catalyst, (D) inorganic filler, (E) epoxy resin, (F) ethylenically unsaturated bond-containing resin, and (G) thermoplastic resin in the resin composition is preferably 80 mass% or more, more preferably 85 mass% or more, even more preferably 90 mass% or more, still more preferably 95 mass% or more, still more preferably 98 mass% or more, and particularly preferably 99 mass% or more, when the total nonvolatile components in the resin composition is 100 mass%.
[0167] <(H) Radical Polymerization Initiator> The resin composition of the present invention may contain (H) a radical polymerization initiator as an optional component. The (H) radical polymerization initiator is preferably, for example, a thermal polymerization initiator that generates free radicals when heated. The (H) radical polymerization initiator may be used alone or in any combination of two or more kinds.
[0168] (H) Examples of the radical polymerization initiator include peroxide-based radical polymerization initiators, azo-based radical polymerization initiators, etc. Among these, peroxide-based radical polymerization initiators are preferred.
[0169] Examples of the peroxide radical polymerization initiator include hydroperoxide compounds such as 1,1,3,3-tetramethylbutyl hydroperoxide; dialkyl peroxide compounds such as tert-butylcumyl peroxide, di-tert-butyl peroxide, di-tert-hexyl peroxide, dicumyl peroxide, 1,4-bis(1-tert-butylperoxy-1-methylethyl)benzene, and 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane; and diacyl peroxide compounds such as dilauroyl peroxide, didecanoyl peroxide, dicyclohexyl peroxydicarbonate, and bis(4-tert-butylcyclohexyl)peroxydicarbonate. peroxyester compounds such as tert-butyl peroxyacetate, tert-butyl peroxybenzoate, tert-butyl peroxyisopropyl monocarbonate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxyneodecanoate, tert-hexylperoxyisopropyl monocarbonate, tert-butyl peroxylaurate, (1,1-dimethylpropyl)2-ethylperhexanoate, tert-butyl 2-ethylperhexanoate, tert-butyl 3,5,5-trimethylperhexanoate, tert-butylperoxy-2-ethylhexyl monocarbonate, and tert-butylperoxymaleic acid.
[0170] Examples of the azo radical polymerization initiator include azonitrile compounds such as 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 1-[(1-cyano-1-methylethyl)azo]formamide, and 2-phenylazo-4-methoxy-2,4-dimethyl-valeronitrile; 2,2'-azobis[2-methyl-N-[1,1-bis(hydroxymethyl)-2-hydroxyethyl]propionamide], 2,2'-azobis[2-methyl-N-[1,1-bis(hydroxymethyl)-2-hydroxyethyl]propionamide], and the like. azo amide compounds such as 2,2'-azobis[2-methyl-N-[2-(1-hydroxybutyl)]-propionamide], 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)-propionamide], 2,2'-azobis(2-methylpropionamide) dihydrate, 2,2'-azobis[N-(2-propenyl)-2-methylpropionamide], 2,2'-azobis(N-butyl-2-methylpropionamide), and 2,2'-azobis(N-cyclohexyl-2-methylpropionamide); alkyl azo compounds such as 2,2'-azobis(2,4,4-trimethylpentane) and 2,2'-azobis(2-methylpropane); and the like.
[0171] (H) Commercially available radical polymerization initiators include, for example, “Perbutyl C”, “Perbutyl A”, “Perbutyl P”, “Perbutyl L”, “Perbutyl O”, “Perbutyl ND”, “Perbutyl Z”, “Perbutyl I”, “Percumyl P”, “Percumyl D”, “Perhexyl D”, “Perhexyl A”, “Perhexyl I”, “Perhexyl Z”, “Perhexyl ND”, “Perhexyl O”, and “Perhexyl PV”, all manufactured by NOF Corporation.
[0172] The content of the (H) radical polymerization initiator in the resin composition is not particularly limited, but, when the non-volatile components in the resin composition are taken as 100 mass%, it is preferably 1 mass% or less, more preferably 0.5 mass% or less, even more preferably 0.1 mass% or less, even more preferably 0.05 mass% or less, and particularly preferably 0.03 mass% or less. The lower limit is not particularly limited, but, when the non-volatile components in the resin composition are taken as 100 mass%, it can be, for example, 0 mass% or more, 0.0001 mass% or more, preferably 0.0005 mass% or more, more preferably 0.001 mass% or more, even more preferably 0.005 mass% or more, and particularly preferably 0.01 mass% or more.
[0173] <(I) Other additives> The resin composition of the present invention may further contain any additive. Examples of such additives include curing catalysts other than imidazole-based curing catalysts, such as phosphorus-based curing catalysts, urea-based curing catalysts, guanidine-based curing catalysts, metal-based curing catalysts, and amine-based curing catalysts; organic fillers such as rubber particles; organometallic compounds such as organocopper compounds, organozinc compounds, and organocobalt compounds; colorants such as phthalocyanine blue, phthalocyanine green, iodine green, diazo yellow, crystal violet, titanium oxide, and carbon black; polymerization inhibitors such as hydroquinone, catechol, pyrogallol, and phenothiazine; leveling agents such as silicone-based leveling agents and acrylic polymer-based leveling agents; thickeners such as bentone and montmorillonite; defoamers such as silicone-based defoamers, acrylic defoamers, fluorine-based defoamers, and vinyl resin-based defoamers; ultraviolet absorbers such as benzotriazole-based ultraviolet absorbers; and adhesion improvers such as urea silane. antioxidants such as hindered phenol antioxidants; fluorescent brightening agents such as stilbene derivatives; surfactants such as fluorine-based surfactants and silicone-based surfactants; flame retardants such as phosphorus-based flame retardants (e.g., phosphate ester compounds, phosphazene compounds, phosphinic acid compounds, red phosphorus), nitrogen-based flame retardants (e.g., melamine sulfate), halogen-based flame retardants, inorganic flame retardants (e.g., antimony trioxide); dispersants such as phosphate ester-based dispersants, polyoxyalkylene-based dispersants, acetylene-based dispersants, silicone-based dispersants, anionic dispersants, and cationic dispersants; stabilizers such as borate-based stabilizers, titanate-based stabilizers, aluminate-based stabilizers, zirconate-based stabilizers, isocyanate-based stabilizers, carboxylic acid-based stabilizers, and carboxylic acid anhydride-based stabilizers. The (I) other additives may be used alone or in any combination of two or more kinds at any ratio. The content of the (I) other additives can be appropriately determined by a person skilled in the art.
[0174] <(J) Organic solvent> The resin composition of the present invention may further contain an arbitrary organic solvent. As the (J) organic solvent, a known one may be appropriately used, and the type is not particularly limited. As the (J) organic solvent, for example, ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, etc.; ester-based solvents such as methyl acetate, ethyl acetate, butyl acetate, isobutyl acetate, isoamyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, etc.; ether-based solvents such as tetrahydropyran, tetrahydrofuran, 1,4-dioxane, diethyl ether, diisopropyl ether, dibutyl ether, diphenyl ether, anisole, etc.; alcohol-based solvents such as methanol, ethanol, propanol, butanol, ethylene glycol, etc.; 2-ethoxyethyl acetate, propylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, ethyl diglycol acetate, γ-butyrolactone, methoxypropionic acid, etc. Examples of the organic solvent include ether ester solvents such as methyl lactate, ethyl lactate, and methyl 2-hydroxyisobutyrate; ether alcohol solvents such as 2-methoxypropanol, 2-methoxyethanol, 2-ethoxyethanol, propylene glycol monomethyl ether, and diethylene glycol monobutyl ether (butylcarbitol); amide solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone; sulfoxide solvents such as dimethyl sulfoxide; nitrile solvents such as acetonitrile and propionitrile; aliphatic hydrocarbon solvents such as hexane, cyclopentane, cyclohexane, and methylcyclohexane; and aromatic hydrocarbon solvents such as benzene, toluene, xylene, ethylbenzene, and trimethylbenzene. (J) The organic solvent may be used alone or in combination of two or more in any ratio.
[0175] The content of the (J) organic solvent in the varnish-like resin composition before drying is not particularly limited, but is, for example, 40% by mass or less, 30% by mass or less, preferably 20% by mass or less, more preferably 10% by mass or less, even more preferably 8% by mass or less, and particularly preferably 6% by mass or less, when the total components in the resin composition are 100% by mass. The content of the (J) organic solvent in the resin composition after drying to form a resin composition layer in the resin sheet is not particularly limited, but is preferably 5% by mass or less, more preferably 3% by mass or less, even more preferably 2% by mass or less, and particularly preferably 1% by mass or less, when the total components in the resin composition are 100% by mass.
[0176] <Method of producing resin composition> The resin composition of the present invention can be produced, for example, by adding (A) maleimide resin, (B) anionically polymerizable curing agent, (C) imidazole-based curing catalyst, (D) inorganic filler, if necessary (E) epoxy resin, if necessary (F) ethylenically unsaturated bond-containing resin, if necessary (G) thermoplastic resin, if necessary (H) radical polymerization initiator, if necessary (I) other additives, if necessary, and if necessary (J) organic solvent in any preparation vessel in any order and / or all at once and mixing. In addition, the temperature can be appropriately set during the process of adding and mixing each component, and heating and / or cooling may be performed temporarily or throughout. In addition, during or after the process of adding and mixing, the resin composition may be stirred or shaken using a stirring device or shaking device such as a mixer to disperse uniformly. In addition, degassing may be performed under low pressure conditions such as under vacuum at the same time as stirring or shaking.
[0177] <Characteristics of resin composition> The resin composition of the present invention comprises (A) a maleimide resin, (B) an anionic polymerizable curing agent, (C) an imidazole-based curing catalyst, and (D) an inorganic filler, the content of the (D) component being 50% by mass or more when the total nonvolatile components in the resin composition are taken as 100% by mass, the maleimide group of the (A) component is 0.1 to 100 molar equivalents per molar equivalent of the reactive group of the (B) component, and the content of the (E) epoxy resin being 0 to 1% by mass when the total nonvolatile components in the resin composition excluding the (D) component are taken as 100% by mass. With such a resin composition, a cured product having a low dielectric tangent and excellent mechanical strength and copper adhesion can be obtained.
[0178] The cured product of the resin composition of the present invention has excellent mechanical strength. For example, the strength at break of the cured product of the resin composition when the tensile strength is measured according to JIS K7127 as in Test Example 3 described later can be preferably 50 MPa or more, more preferably 70 MPa or more, even more preferably 80 MPa or more, even more preferably 90 MPa or more, even more preferably 95 MPa or more, particularly preferably 100 MPa or more, and particularly preferably 105 MPa or more. For example, the elongation at break of the cured product of the resin composition when the tensile strength is measured according to JIS K7127 as in Test Example 3 described later can be preferably 0.5% or more, more preferably 1.0% or more, even more preferably 1.3% or more, even more preferably 1.5% or more, and particularly preferably 1.7% or more.
[0179] The cured product of the resin composition of the present invention has a low dielectric loss tangent. For example, the dielectric loss tangent (Df) of the cured product of the resin composition measured at 5.8 GHz and 23° C. as in Test Example 1 described later is preferably 0.01 or less, more preferably 0.007 or less, even more preferably 0.005 or less, still more preferably 0.004 or less, and particularly preferably 0.0035 or less.
[0180] The cured product of the resin composition of the present invention has excellent copper adhesion (copper foil peel strength). For example, as in the following Test Example 4, after copper foil is laminated on the cured product, the copper foil is pulled in the vertical direction and peeled off. The copper foil peel strength calculated based on JIS C6481 from the load is preferably 0.2 kgf / cm or more, more preferably 0.3 kgf / cm or more, even more preferably 0.4 kgf / cm or more, even more preferably 0.45 kgf / cm or more, and particularly preferably 0.5 kgf / cm or more.
[0181] In one embodiment, the cured product of the resin composition of the present invention may have a low relative dielectric constant. In one embodiment, for example, the relative dielectric constant (Dk) of the cured product of the resin composition measured at 5.8 GHz and 23° C. as in Test Example 1 described later may be preferably 5.0 or less, more preferably 4.5 or less, even more preferably 4.0 or less, even more preferably 3.5 or less, even more preferably 3.3 or less, particularly preferably 3.2 or less, and particularly preferably 3.1 or less.
[0182] In one embodiment, the cured product of the resin composition of the present invention may be characterized by a high glass transition temperature (Tg). In one embodiment, the glass transition temperature (Tg) measured, for example, as in Test Example 2 below, may be preferably 100° C. or higher, more preferably 120° C. or higher, even more preferably 130° C. or higher, even more preferably 140° C. or higher, even more preferably 150° C. or higher, and particularly preferably 160° C. or higher.
[0183] <Applications of resin composition> The resin composition of the present invention can be suitably used as a resin composition for insulating purposes, particularly as a resin composition for forming an insulating layer. Specifically, it can be suitably used as a resin composition for forming an insulating layer (resin composition for forming an insulating layer for forming a conductor layer) for forming a conductor layer (including a rewiring layer) formed on an insulating layer. In addition, in a printed wiring board described later, it can be suitably used as a resin composition for forming an insulating layer of a printed wiring board (resin composition for forming an insulating layer of a printed wiring board). The resin composition of the present invention can also be used in a wide range of applications requiring a resin composition, such as a resin sheet, a sheet-like laminate material such as a prepreg, a solder resist, an underfill material, a die bonding material, a semiconductor encapsulant, a hole filling resin, and a component embedding resin.
[0184] In addition, for example, when a semiconductor chip package is manufactured through the following steps (1) to (6), the resin composition of the present invention can be suitably used as a resin composition for a rewiring formation layer (resin composition for forming a rewiring formation layer) as an insulating layer for forming a rewiring layer, and as a resin composition for sealing a semiconductor chip (resin composition for sealing a semiconductor chip). When a semiconductor chip package is manufactured, a rewiring layer may be further formed on the sealing layer. (1) A step of laminating a temporary fixing film onto a substrate; (2) a step of temporarily fixing a semiconductor chip on a temporary fixing film; (3) forming an encapsulation layer on the semiconductor chip; (4) peeling the substrate and the temporary fixing film from the semiconductor chip; (5) forming a rewiring formation layer as an insulating layer on the surface of the semiconductor chip from which the base material and the temporary fixing film have been peeled off; and (6) A process of forming a rewiring layer as a conductor layer on the rewiring formation layer.
[0185] Furthermore, the resin composition of the present invention provides an insulating layer with good component embedding properties, and therefore can be suitably used when the printed wiring board is a circuit board with built-in components.
[0186] <Sheet-type laminated material> The resin composition of the present invention can be used by coating in the form of a varnish, but from an industrial perspective, it is generally preferred to use the resin composition in the form of a sheet-like laminate material containing the resin composition.
[0187] As the sheet-like laminate material, the following resin sheets and prepregs are preferred.
[0188] In one embodiment, the resin sheet includes a support and a resin composition layer provided on the support, and the resin composition layer is formed from the resin composition of the present invention.
[0189] The thickness of the resin composition layer is preferably 50 μm or less, more preferably 40 μm or less, from the viewpoint of making the printed wiring board thinner and being able to provide a cured product with excellent insulation even if the cured product of the resin composition is a thin film. The lower limit of the thickness of the resin composition layer is not particularly limited, but can usually be 5 μm or more, 10 μm or more, etc.
[0190] Examples of the support include films made of plastic materials, metal foils, and release papers, with films made of plastic materials and metal foils being preferred.
[0191] When a film made of a plastic material is used as the support, examples of the plastic material include polyesters such as polyethylene terephthalate (hereinafter sometimes abbreviated as "PET") and polyethylene naphthalate (hereinafter sometimes abbreviated as "PEN"), polycarbonate (hereinafter sometimes abbreviated as "PC"), acrylics such as polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, polyimide, etc. Among these, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.
[0192] When a metal foil is used as the support, examples of the metal foil include copper foil, aluminum foil, etc., and copper foil is preferred. As the copper foil, a foil made of a single metal, copper, or an alloy of copper and another metal (e.g., tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.) may be used.
[0193] The surface of the support to be bonded to the resin composition layer may be subjected to a matte treatment, a corona treatment, or an antistatic treatment.
[0194] In addition, as the support, a support with a release layer having a release layer on the surface to be bonded to the resin composition layer may be used. The release agent used in the release layer of the support with a release layer may be, for example, one or more release agents selected from the group consisting of alkyd resins, polyolefin resins, urethane resins, and silicone resins. The support with a release layer may be a commercially available product, for example, "SK-1", "AL-5", and "AL-7" manufactured by Lintec Corporation, "Lumirror T60" manufactured by Toray Industries, Inc., "Purex" manufactured by Teijin Limited, and "Unipeel" manufactured by Unitika Limited, which are PET films having a release layer mainly composed of an alkyd resin-based release agent.
[0195] The thickness of the support is not particularly limited, but is preferably in the range of 5 μm to 75 μm, and more preferably in the range of 10 μm to 60 μm. When a support with a release layer is used, it is preferable that the total thickness of the support with a release layer is in the above range.
[0196] In one embodiment, the resin sheet may further include an optional layer as necessary. For example, such an optional layer may be a protective film equivalent to the support provided on the surface of the resin composition layer that is not bonded to the support (i.e., the surface opposite to the support). The thickness of the protective film is not particularly limited, but is, for example, 1 μm to 40 μm. By laminating the protective film, adhesion of dirt and the like to the surface of the resin composition layer and scratches can be suppressed.
[0197] The resin sheet can be produced, for example, by preparing a liquid (varnish-like) resin composition as is or by dissolving the resin composition in an organic solvent to prepare a liquid (varnish-like) resin composition, applying this onto a support using a die coater or the like, and then drying to form a resin composition layer.
[0198] The organic solvent may be the same as the organic solvent described as a component of the resin composition. The organic solvent may be used alone or in combination of two or more kinds.
[0199] Drying may be performed by a known method such as heating or hot air blowing. Drying conditions are not particularly limited, but drying is performed so that the content of the organic solvent in the resin composition layer becomes 10 mass % or less, preferably 5 mass % or less. Although it varies depending on the boiling point of the organic solvent in the resin composition, for example, when a resin composition containing 30 mass % to 60 mass % of the organic solvent is used, the resin composition layer can be formed by drying at 50°C to 150°C for 3 minutes to 10 minutes.
[0200] The resin sheet can be stored in a rolled state. When the resin sheet has a protective film, it can be used by peeling off the protective film.
[0201] In one embodiment, the prepreg is formed by impregnating a sheet-like fiber substrate with the resin composition of the present invention.
[0202] The sheet-like fiber substrate used for the prepreg is not particularly limited, and can be a substrate commonly used for prepreg, such as glass cloth, aramid nonwoven fabric, liquid crystal polymer nonwoven fabric, etc. From the viewpoint of thinning the printed wiring board, the thickness of the sheet-like fiber substrate is preferably 50 μm or less, more preferably 40 μm or less, even more preferably 30 μm or less, and particularly preferably 20 μm or less. The lower limit of the thickness of the sheet-like fiber substrate is not particularly limited. It is usually 10 μm or more.
[0203] The prepreg can be produced by a known method such as a hot melt method or a solvent method.
[0204] The thickness of the prepreg may be in the same range as that of the resin composition layer in the above-mentioned resin sheet.
[0205] The sheet-like laminate material of the present invention can be suitably used for forming an insulating layer of a printed wiring board (for an insulating layer of a printed wiring board), and can be more suitably used for forming an interlayer insulating layer of a printed wiring board (for an interlayer insulating layer of a printed wiring board).
[0206] <Printed wiring board> The printed wiring board of the present invention includes an insulating layer made of a cured product obtained by curing the resin composition of the present invention.
[0207] The printed wiring board can be produced, for example, by using the above-mentioned resin sheet by a method including the following steps (I) and (II). (I) A step of laminating a resin sheet on an inner layer substrate such that a resin composition layer of the resin sheet is bonded to the inner layer substrate. (II) A step of curing (e.g., heat curing) the resin composition layer to form an insulating layer.
[0208] The "inner layer substrate" used in step (I) is a member that becomes the substrate of the printed wiring board, and examples thereof include a glass epoxy substrate, a metal substrate, a polyester substrate, a polyimide substrate, a BT resin substrate, and a thermosetting polyphenylene ether substrate. The substrate may have a conductor layer on one or both sides, and the conductor layer may be patterned. An inner layer substrate having a conductor layer (circuit) formed on one or both sides of the substrate may be called an "inner layer circuit substrate". In addition, an intermediate product on which an insulating layer and / or a conductor layer is to be formed during the manufacture of a printed wiring board is also included in the "inner layer substrate" of the present invention. When the printed wiring board is a circuit board with built-in components, an inner layer substrate with built-in components may be used.
[0209] The lamination of the inner layer substrate and the resin sheet can be carried out, for example, by thermocompression bonding the resin sheet to the inner layer substrate from the support side. Examples of the member for thermocompression bonding the resin sheet to the inner layer substrate (hereinafter also referred to as the "thermocompression bonding member") include a heated metal plate (such as a SUS plate) or a metal roll (SUS roll). It is preferable to press the thermocompression member not directly onto the resin sheet, but via an elastic material such as heat-resistant rubber so that the resin sheet can sufficiently follow the surface irregularities of the inner layer substrate.
[0210] The lamination of the inner layer substrate and the resin sheet may be performed by a vacuum lamination method. In the vacuum lamination method, the thermocompression temperature is preferably in the range of 60°C to 160°C, more preferably in the range of 80°C to 140°C, the thermocompression pressure is preferably in the range of 0.098MPa to 1.77MPa, more preferably in the range of 0.29MPa to 1.47MPa, and the thermocompression time is preferably in the range of 20 seconds to 400 seconds, more preferably in the range of 30 seconds to 300 seconds. The lamination may be performed under reduced pressure conditions, preferably at a pressure of 26.7hPa or less.
[0211] The lamination can be performed by a commercially available vacuum laminator, such as a vacuum pressure laminator manufactured by Meiki Seisakusho Co., Ltd., a vacuum applicator manufactured by Nikko Materials Co., Ltd., or a batch type vacuum pressure laminator.
[0212] After lamination, the laminated resin sheet may be smoothed under normal pressure (atmospheric pressure), for example, by pressing a thermocompression member from the support side. The pressing conditions for the smoothing treatment may be the same as the thermocompression conditions for the lamination. The smoothing treatment may be performed using a commercially available laminator. The lamination and smoothing treatment may be performed consecutively using the commercially available vacuum laminator.
[0213] The support may be removed between step (I) and step (II) or after step (II).
[0214] In step (II), the resin composition layer is cured (for example, thermally cured) to form an insulating layer made of a cured product of the resin composition. The curing conditions for the resin composition layer are not particularly limited, and conditions that are usually adopted when forming an insulating layer for a printed wiring board may be used.
[0215] For example, the thermal curing conditions for the resin composition layer vary depending on the type of resin composition, etc., but in one embodiment, the curing temperature is preferably 120° C. to 240° C., more preferably 150° C. to 220° C., and even more preferably 170° C. to 210° C. The curing time is preferably 5 minutes to 120 minutes, more preferably 10 minutes to 100 minutes, and even more preferably 15 minutes to 100 minutes.
[0216] Before the resin composition layer is thermally cured, the resin composition layer may be preheated at a temperature lower than the curing temperature. For example, prior to thermally curing the resin composition layer, the resin composition layer may be preheated at a temperature of 50° C. to 120° C., preferably 60° C. to 115° C., more preferably 70° C. to 110° C. for 5 minutes or more, preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes, and even more preferably 15 minutes to 100 minutes.
[0217] In manufacturing a printed wiring board, the steps of (III) drilling holes in the insulating layer, (IV) roughening the insulating layer, and (V) forming a conductor layer may be further carried out. These steps (III) to (V) may be carried out according to various methods known to those skilled in the art for use in manufacturing printed wiring boards. When the support is removed after step (II), the support may be removed between step (II) and step (III), between step (III) and step (IV), or between step (IV) and step (V). In addition, the formation of the insulating layer and the conductor layer in steps (II) to (V) may be repeated to form a multilayer wiring board, as necessary.
[0218] In another embodiment, the printed wiring board of the present invention can be manufactured using the above-mentioned prepreg. The manufacturing method is basically the same as when a resin sheet is used.
[0219] Step (III) is a step of drilling holes in the insulating layer, which allows holes such as via holes and through holes to be formed in the insulating layer. Step (III) may be performed using, for example, a drill, a laser, plasma, etc., depending on the composition of the resin composition used to form the insulating layer. The dimensions and shape of the holes may be appropriately determined depending on the design of the printed wiring board.
[0220] Step (IV) is a step of roughening the insulating layer. Usually, smears are also removed in this step (IV). The procedure and conditions of the roughening treatment are not particularly limited, and known procedures and conditions that are usually used when forming an insulating layer of a printed wiring board can be adopted. For example, the insulating layer can be roughened by carrying out a swelling treatment with a swelling liquid, a roughening treatment with an oxidizing agent, and a neutralization treatment with a neutralizing liquid in this order.
[0221] The swelling liquid used in the roughening treatment is not particularly limited, but includes an alkaline solution, a surfactant solution, etc., and is preferably an alkaline solution, and more preferably a sodium hydroxide solution or a potassium hydroxide solution. Examples of commercially available swelling liquids include "Swelling Dip Securigans P" and "Swelling Dip Securigans SBU" manufactured by Atotech Japan. The swelling treatment using the swelling liquid is not particularly limited, but can be performed by immersing the insulating layer in a swelling liquid at 30°C to 90°C for 1 to 20 minutes, for example. From the viewpoint of suppressing the swelling of the resin of the insulating layer to an appropriate level, it is preferable to immerse the insulating layer in a swelling liquid at 40°C to 80°C for 5 to 15 minutes.
[0222] The oxidizing agent used in the roughening treatment is not particularly limited, but examples thereof include an alkaline permanganate solution in which potassium permanganate or sodium permanganate is dissolved in an aqueous solution of sodium hydroxide. The roughening treatment using an oxidizing agent such as an alkaline permanganate solution is preferably performed by immersing the insulating layer in an oxidizing agent solution heated to 60°C to 100°C for 10 minutes to 30 minutes. The concentration of permanganate in the alkaline permanganate solution is preferably 5% by mass to 10% by mass. Examples of commercially available oxidizing agents include alkaline permanganate solutions such as "Concentrate Compact CP" and "Dosing Solution Securigans P" manufactured by Atotech Japan.
[0223] The neutralizing solution used in the roughening treatment is preferably an acidic aqueous solution, and a commercially available product such as "Reduction Solution Securigant P" manufactured by Atotech Japan can be mentioned.
[0224] The treatment with the neutralizing solution can be carried out by immersing the surface that has been roughened with an oxidizing agent in a neutralizing solution at 30° C. to 80° C. for 5 to 30 minutes. From the viewpoint of workability, etc., a method in which the object that has been roughened with an oxidizing agent is immersed in a neutralizing solution at 40° C. to 70° C. for 5 to 20 minutes is preferred.
[0225] In one embodiment, the arithmetic mean roughness (Ra) of the insulating layer surface after the roughening treatment is not particularly limited, but is preferably 500 nm or less, more preferably 400 nm or less, and even more preferably 300 nm or less. The lower limit is not particularly limited, and may be, for example, 1 nm or more, 2 nm or more, etc. The root mean square roughness (Rq) of the insulating layer surface after the roughening treatment is preferably 500 nm or less, more preferably 400 nm or less, and even more preferably 300 nm or less. The lower limit is not particularly limited, and may be, for example, 1 nm or more, 2 nm or more, etc. The arithmetic mean roughness (Ra) and root mean square roughness (Rq) of the insulating layer surface can be measured using a non-contact surface roughness meter.
[0226] Step (V) is a step of forming a conductor layer, and the conductor layer is formed on the insulating layer. The conductor material used for the conductor layer is not particularly limited. In a preferred embodiment, the conductor layer contains one or more metals selected from the group consisting of gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin and indium. The conductor layer may be a single metal layer or an alloy layer, and examples of the alloy layer include layers formed from alloys of two or more metals selected from the above group (e.g., nickel-chromium alloy, copper-nickel alloy and copper-titanium alloy). Among these, from the viewpoints of versatility in forming the conductor layer, cost, ease of patterning, and the like, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or an alloy layer of a nickel-chromium alloy, a copper-nickel alloy, or a copper-titanium alloy is preferred, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or an alloy layer of a nickel-chromium alloy is more preferred, and a single metal layer of copper is even more preferred.
[0227] The conductor layer may be a single-layer structure or a multi-layer structure in which two or more single metal layers or alloy layers made of different kinds of metals or alloys are laminated. When the conductor layer has a multi-layer structure, the layer in contact with the insulating layer is preferably a single metal layer of chromium, zinc or titanium, or an alloy layer of a nickel-chromium alloy.
[0228] The thickness of the conductor layer depends on the desired design of the printed wiring board, but is generally 3 μm to 35 μm, and preferably 5 μm to 30 μm.
[0229] In one embodiment, the conductor layer may be formed by plating. For example, a conductor layer having a desired wiring pattern can be formed by plating the surface of the insulating layer by a conventionally known technique such as a semi-additive method or a full-additive method, and from the viewpoint of ease of production, it is preferable to form the conductor layer by the semi-additive method. An example of forming the conductor layer by the semi-additive method will be described below.
[0230] First, a plating seed layer is formed on the surface of an insulating layer by electroless plating. Next, a mask pattern is formed on the formed plating seed layer to expose a part of the plating seed layer corresponding to a desired wiring pattern. After a metal layer is formed on the exposed plating seed layer by electrolytic plating, the mask pattern is removed. Thereafter, unnecessary plating seed layer is removed by etching or the like to form a conductor layer having a desired wiring pattern.
[0231] In another embodiment, the conductor layer may be formed using a metal foil. When the conductor layer is formed using a metal foil, it is preferable to carry out step (V) between steps (I) and (II). For example, after step (I), the support is removed, and a metal foil is laminated on the exposed surface of the resin composition layer. The lamination of the resin composition layer and the metal foil may be carried out by a vacuum lamination method. The lamination conditions may be the same as those described for step (I). Next, step (II) is carried out to form an insulating layer. Thereafter, a conductor layer having a desired wiring pattern can be formed by a conventionally known technique such as a subtractive method or a modified semi-additive method, using the metal foil on the insulating layer.
[0232] The metal foil can be produced by a known method such as an electrolytic method, a rolling method, etc. Commercially available metal foils include, for example, HLP foil and JXUT-III foil manufactured by JX Nippon Mining & Metals Corporation, and 3EC-III foil and TP-III foil manufactured by Mitsui Mining & Smelting Co., Ltd.
[0233] <Semiconductor device> The semiconductor device of the present invention includes the printed wiring board of the present invention. The semiconductor device of the present invention can be manufactured by using the printed wiring board of the present invention.
[0234] Examples of the semiconductor device include various semiconductor devices used in electric appliances (for example, computers, mobile phones, digital cameras, and televisions) and vehicles (for example, motorcycles, automobiles, trains, ships, and aircraft). EXAMPLES
[0235] The present invention will be specifically described below with reference to examples. The present invention is not limited to these examples. In the following, "parts" and "%" representing amounts mean "parts by mass" and "% by mass", respectively, unless otherwise specified. Unless otherwise specified, the temperature conditions are room temperature (23°C), and unless otherwise specified, the pressure conditions are atmospheric pressure (1 atm).
[0236] <Synthesis Example 1: Synthesis of Maleimide A> Maleimide A (m = 1.47, Mw / Mn = 1.81) represented by the following formula was synthesized in the same manner as in Synthesis Example 1 of the Japan Institute of Invention and Innovation Disclosure Technical Journal Publication No. 2020-500211, and a MEK solution of maleimide resin (non-volatile components 62% by mass) was obtained.
[0237] [ka]
[0238] <Synthesis Example 2: Synthesis of Phenol B> In a 1L reaction vessel equipped with a thermometer, stirrer, and cooling tube, 410g of methanol, 48.0g of sodium hydroxide, and 205.0g of biphenol were charged, and 91.8g of allyl chloride was added dropwise at 40°C over 3 hours while being careful of heat generation. The temperature was then raised to the temperature at which methanol refluxes (about 60°C), and an allyl etherification reaction was carried out for 4 hours. Next, after removing salt by washing with water, the temperature was raised to 180°C, and a transfer reaction was carried out for 10 hours. After the transfer reaction, the temperature was lowered to 100°C, 205.0g of butanol was added to dissolve the resin, and 70.5g of potassium hydroxide was added, and a propenylation reaction was carried out at 115°C for 6 hours. The mixture was then washed with water and concentrated to obtain "phenol B" (propenyl form of biphenol).
[0239] [ka]
[0240] <Synthesis Example 3: Synthesis of ester compound C> In a reaction vessel, 89 parts by mass of ortho-allylphenol, 110 parts by mass of dicyclopentadiene-phenol copolymer resin (softening point 85°C, hydroxyl group equivalent approximately 165g / eq.), and 1000 parts by mass of toluene were charged, and dissolved while the inside of the vessel was purged with nitrogen under reduced pressure. Then, 135 parts by mass of isophthalic acid chloride was charged and dissolved. Next, 0.5g of tetrabutylammonium bromide was added, and 309g of 20% aqueous sodium hydroxide solution was dropped over 3 hours while purging the inside of the vessel with nitrogen. At that time, the temperature in the system was controlled to 60°C or less. Then, the mixture was stirred for 1 hour to react. After the reaction was completed, the reaction mixture was separated and the aqueous layer was removed. This operation was repeated until the pH of the aqueous layer became 7, and toluene, etc. were distilled off under heating and reduced pressure conditions to obtain ester compound C (unsaturated bond equivalent 428g / eq.) containing an aromatic ester skeleton and an unsaturated bond.
[0241] <Synthesis Example 4: Synthesis of vinyl resin D> 3.0 mol (390.6 g) of divinylbenzene, 1.8 mol (229.4 g) of ethylvinylbenzene, 10.2 mol (1066.3 g) of styrene, and 15.0 mol (1532.0 g) of n-propyl acetate were charged into a 5.0 L reactor, and 600 mmol of a diethyl ether complex of boron trifluoride was added at 70 ° C. and reacted for 4 hours. After the polymerization solution was stopped with an aqueous sodium hydrogen carbonate solution, the oil layer was washed three times with pure water, and the polymer was recovered by degassing under reduced pressure at 60 ° C. The obtained product was weighed, and it was confirmed that 896.7 g of vinyl compound C was obtained. The weight average molecular weight (Mw) of vinyl compound D was 41,300.
[0242] <Synthesis Example 5: Synthesis of Polyimide E> A 500 mL separable flask equipped with a water content receiver connected to a reflux condenser, a nitrogen inlet tube, and a stirrer was prepared. 20.3 g of 4,4'-oxydiphthalic anhydride (ODPA), 200 g of γ-butyrolactone, 20 g of toluene, and 29.6 g of 5-(4-aminophenoxy)-3-[4-(4-aminophenoxy)phenyl]-1,1,3-trimethylindane were added to this flask, and the mixture was stirred at 45°C for 2 hours under a nitrogen stream to carry out a reaction. Next, the reaction solution was heated and, while maintaining the temperature at about 160°C, condensed water was azeotropically removed together with toluene under a nitrogen stream. It was confirmed that a predetermined amount of water had accumulated in the water content receiver and that no water was flowing out. After confirmation, the reaction solution was further heated and stirred at 200°C for 1 hour. The mixture was then cooled to obtain a polyimide solution (non-volatile content: 20% by mass) containing polyimide E having a 1,1,3-trimethylindane skeleton. The weight-average molecular weight of polyimide E was 12,000.
[0243] <Examples 1 to 5 and Comparative Examples 1 to 5: Preparation of resin compositions> Each component was weighed out in the mixing ratio in parts by mass shown in Table 1, and then 10 parts of MEK and 10 parts of cyclohexanone were mixed and uniformly dispersed using a high-speed rotating mixer to prepare a varnish-like resin composition. The details of each component shown in Table 1 are as follows.
[0244] (A) Maleimide resin MIR-3000-70MT: Maleimide resin with biphenyl skeleton, maleimide group equivalent weight 393g / eq., non-volatile content 70% by mass in toluene solution, manufactured by Nippon Kayaku Co., Ltd. Maleimide A: Maleimide resin having an indane skeleton, maleimide group equivalent weight 428 g / eq., synthesized in Synthesis Example 1 BMI-2300: Maleimide resin with bismaleimide diphenylmethane structure, maleimide group equivalent weight 179g / eq., manufactured by Daiwa Chemical Industry Co., Ltd. SLK-6895-T90: Maleimide resin with a carbon skeleton derived from dimer acid, maleimide group equivalent weight 345g / eq., non-volatile content 90% by mass in toluene solution, manufactured by Shin-Etsu Chemical Co., Ltd.
[0245] (B) Anionic polymerizable curing agent LA-3018-50P: Phenol-based hardener, functional group equivalent weight 151g / eq., non-volatile content 50% by mass in 1-methoxy-2-propanol solution, manufactured by DIC Corporation ALP-d: Benzoxazine-based curing agent, functional group equivalent weight 257g / eq., manufactured by Shikoku Kasei Co., Ltd. SA90: Phenol-based hardener, functional group equivalent weight 800g / eq., manufactured by SABIC Phenol B: Phenol-based hardener, functional group equivalent weight 133g / eq., synthesized in Synthesis Example 2 Ester compound C: Active ester-based curing agent, functional group equivalent weight 214g / eq., toluene solution with 70% solids, manufactured by DIC Corporation V-03: Carbodiimide-based curing agent, functional group equivalent weight 216g / eq., non-volatile content 50% by mass in toluene solution, manufactured by Nisshinbo Chemical Co., Ltd. WA: Amine-based curing agent, functional group equivalent weight 45g / eq., manufactured by DIC Corporation
[0246] (C) Imidazole-based curing catalyst 1B2PZ: 1-benzyl-2-phenylimidazole, manufactured by Shikoku Chemical Industry Co., Ltd. 2P4MZ: 2-phenyl-4-methylimidazole, manufactured by Shikoku Chemical Industry Co., Ltd. C11Z-A: 2,4-diamino-6-(2-undecyl-1-imidazolyl)ethyl-1,3,5-triazine, manufactured by Shikoku Chemical Industry Co., Ltd.
[0247] (D) Inorganic filler SO-C2: Spherical silica surface-treated with an amine-based alkoxysilane compound (Shin-Etsu Chemical Co., Ltd.'s "KBM573"), with an average particle size of 0.5 μm and a specific surface area of 5.8 m 2 / g, manufactured by Admatechs UFP-30: Spherical silica surface-treated with an amine-based alkoxysilane compound (Shin-Etsu Chemical Co., Ltd.'s "KBM573"), with an average particle size of 0.3 μm and a specific surface area of 30.7 m 2 / g, manufactured by Denka - HiPresica FH: Hollow silica surface-treated with an amine-based alkoxysilane compound ("KBM573" manufactured by Shin-Etsu Chemical Co., Ltd.), average particle size 0.5 μm, porosity 30-50%, manufactured by Ube Exsymo Co., Ltd.
[0248] (E) Epoxy resin HP-4032-SS: Naphthalene type epoxy resin, epoxy equivalent 144g / eq., manufactured by DIC Corporation
[0249] (F) Ethylenically unsaturated bond-containing resin Vinyl resin D: polystyrene resin having an ethylenically unsaturated group, synthesized in Synthesis Example 4, non-volatile content 50% by mass CYCLOTENE 2022: Benzocyclobutene resin with ethylenically unsaturated groups, manufactured by The Dow Chemical Company
[0250] (G)Thermoplastic resin PX-3-RP-61: Oxazoline group-containing polymer, manufactured by Nippon Shokubai Co., Ltd. YX7553BH30: Phenoxy resin, 1:1 solution of MEK and cyclohexanone with 30% non-volatile content by mass, manufactured by Mitsubishi Chemical Corporation Polyimide E: Polyimide resin, synthesized in Synthesis Example 5, non-volatile content 20% by mass
[0251] (H) Radical polymerization initiator Perhexyl D: Peroxide radical polymerization initiator, di-tert-hexyl peroxide, NOF Corporation
[0252] <Test Example 1: Measurement of relative dielectric constant (Dk) and dielectric loss tangent (Df)> (1) Preparation of resin sheet A having a resin composition layer thickness of 40 μm A polyethylene terephthalate film with a release layer ("AL5" manufactured by Lintec Corporation, thickness 38 μm) was prepared as a support. On the release layer of this support, the varnish-like resin compositions obtained in the Examples and Comparative Examples were uniformly applied so that the thickness of the resin composition layer after drying was 40 μm. Thereafter, the resin composition was dried at 80°C to 100°C (average 90°C) for 2 minutes to obtain a resin sheet A including a support and a resin composition layer.
[0253] (2) Preparation of hardened product The obtained resin sheet A was cured for 90 minutes in an oven at 190° C. The support was peeled off from the resin sheet A taken out of the oven to obtain a cured product of the resin composition layer.
[0254] (3) Measurement of dielectric constant (Dk) and dielectric loss tangent (Df) The cured product was cut into a piece 80 mm long and 2 mm wide, and the dielectric constant and dielectric tangent (Dk and Df values) were measured by the cavity resonance perturbation method using an Agilent Technologies HP8362B at a measurement frequency of 5.8 GHz and measurement temperatures of 23°C and 90°C. Measurements were performed on two test pieces, and the average was calculated.
[0255] <Test Example 2: Measurement of glass transition temperature (Tg)> The cured product obtained in Test Example 1(2) was cut into test pieces with a width of about 5 mm and a length of about 15 mm, and a thermomechanical analysis was performed by the tensile load method using a thermomechanical analyzer (Rigaku's "Thermo Plus TMA8310"). After mounting the test pieces on the apparatus, the thermal expansion coefficient (ppm) was measured twice consecutively under the measurement conditions of a load of 1 g and a heating rate of 5°C / min. From the thermal expansion coefficient value from 25°C to 150°C in the second measurement, the average linear expansion coefficient (ppm / °C) was calculated, and the glass transition temperature (Tg;°C) was calculated in the second measurement.
[0256] <Test Example 3: Measurement of breaking strength and breaking elongation> The cured product obtained in Test Example 1(2) was subjected to tensile strength measurement using an Orientec tensile tester "RTC-1250A" to measure the strength at break and elongation at break at 23°C. The measurement was performed in accordance with JIS K7127. The measurement was performed five times, and the average of the top three points was calculated.
[0257] <Test Example 4: Measurement of copper foil peel strength> (1) Copper foil preparation The shiny side of an electrolytic copper foil (Mitsui Mining & Metals Co., Ltd. "3EC-III", thickness 35 μm) was etched by 1 μm with a micro-etching agent (Mech Co., Ltd. "CZ8101") to roughen the copper surface, and then anti-rust treatment (CL8300) was performed. The copper foil whose surface was etched with the micro-etching agent in this way may be referred to as "CZ copper foil" hereinafter. Furthermore, this copper foil was heat-treated in an oven at 130°C for 30 minutes to obtain copper foil I having a roughened treated surface.
[0258] (2) Preparation of inner layer board A glass cloth-based epoxy resin double-sided copper-clad laminate (copper foil thickness 18 μm, substrate thickness 0.4 mm, Panasonic "R1515A") was prepared, which had copper foil on its surface and an inner layer circuit formed thereon. Both sides of this glass cloth-based epoxy resin double-sided copper-clad laminate were etched to a thickness of 1 μm with a microetching agent (Mec "CZ8101") to roughen the copper foil surface. This resulted in an inner layer substrate having a CZ copper foil with a treated surface on its surface.
[0259] (3) Lamination of the resin composition layer The resin sheet A prepared in Test Example 1(1) was laminated on both sides of the inner layer substrate. This lamination was performed using a batch-type vacuum pressure laminator (two-stage build-up laminator "CVP700" manufactured by Nikko Materials Co., Ltd.) so that the resin composition layer was in contact with the inner layer substrate. The lamination was performed by reducing the pressure for 30 seconds to adjust the air pressure to 13 hPa or less, and then pressing at 120°C and a pressure of 0.74 MPa for 30 seconds. Next, the laminated resin sheet was heat-pressed at 100°C and a pressure of 0.5 MPa for 60 seconds. Thereafter, the support was peeled off to expose the resin composition layer.
[0260] (4) Lamination of copper foil and curing of resin composition layer The treated surface of the copper foil I was laminated on the exposed resin composition layer under the same conditions as in "(3) Lamination of the resin composition layer" above. The resin composition layer was then cured at 200°C for 90 minutes to form an insulating layer containing a cured product of the resin composition. Through the above operations, an evaluation substrate C was obtained in which CZ copper foil was laminated on both sides of the insulating layer. This evaluation substrate C had a layer structure of copper foil I / insulating layer / inner layer substrate / insulating layer / copper foil I.
[0261] (5) Measurement of copper foil peel strength Evaluation board C was cut into small pieces measuring 150 mm x 30 mm. A cutter was used to make a cut in the small piece of copper foil I, enclosing a section measuring 10 mm in width and 100 mm in length. One end of this section was peeled off and held with the grip of a tensile tester (Autocom universal testing machine "AC-50C-SL" manufactured by TSE Corporation). The copper foil was pulled vertically at a speed of 50 mm / min at room temperature (25°C), and the load [kgf / cm] at which 35 mm was peeled off was measured as the copper foil peel strength. The measurement was performed in accordance with the Japanese Industrial Standard JIS C6481.
[0262] The measurement results of the test examples are summarized in Table 1 below.
[0263] [Table 1]
[0264] From the results shown in Table 1 above, it can be seen that by using a resin composition comprising (A) a maleimide resin, (B) an anionic polymerizable curing agent, (C) an imidazole-based curing catalyst, and (D) an inorganic filler, in which the content of component (D) is 50% by mass or more when the total non-volatile components in the resin composition is taken as 100% by mass, the maleimide groups of component (A) are 0.1 to 100 molar equivalents per molar equivalent of reactive groups of component (B), and the content of epoxy resin (E) is 0 to 1% by mass when the total non-volatile components in the resin composition excluding component (D) is taken as 100% by mass, a cured product with low dielectric tangent and excellent mechanical strength and copper adhesion can be obtained.
Claims
1. A resin composition comprising (A) a maleimide resin, (B) an anionic polymerizable curing agent, (C) an imidazole-based curing catalyst, and (D) an inorganic filler, The content of the (D) component is 50% by mass or more, relative to 100% by mass of all non-volatile components in the resin composition; the amount of maleimide groups in the component (A) is 0.1 to 100 molar equivalents relative to 1 molar equivalent of reactive groups in the component (B); A resin composition, wherein the content of the epoxy resin (E) is 0% by mass to 1% by mass, relative to 100% by mass of non-volatile components in the resin composition excluding the component (D).
2. 2. The resin composition according to claim 1, wherein the maleimide group equivalent of component (A) is 100 g / eq. to 500 g / eq.
3. 2. The resin composition according to claim 1, wherein the component (A) contains a maleimide resin selected from the group consisting of a maleimide resin having a biphenyl skeleton, a maleimide resin having an indane skeleton, a maleimide resin having a bismaleimide diphenylmethane skeleton, a maleimide resin having a carbon skeleton derived from a dimer acid, and a maleimide resin having an aromatic polyether ketone skeleton.
4. The resin composition according to claim 1, wherein the content of the component (A) is 30% by mass or more, based on 100% by mass of non-volatile components excluding the component (D) in the resin composition.
5. 2. The resin composition according to claim 1, wherein the component (B) comprises an anionically polymerizable curing agent selected from the group consisting of a phenolic curing agent, a carbodiimide curing agent, an amine curing agent, a benzoxazine curing agent, and an active ester curing agent.
6. The resin composition according to claim 1 , wherein the component (B) comprises a phenol-based curing agent.
7. The resin composition according to claim 1, wherein the content of the component (B) is 25% by mass or less, based on 100% by mass of non-volatile components excluding the component (D) in the resin composition.
8. 2. The resin composition according to claim 1, wherein the mass ratio of the component (B) to the component (A) (component (B) / component (A)) is 0.05 to 1.
9. The resin composition according to claim 1, wherein the content of the component (C) is 1% by mass to 5% by mass, assuming that the total amount of non-volatile components in the resin composition excluding the component (D) is 100% by mass.
10. The resin composition according to claim 1 , wherein the component (D) comprises silica.
11. The resin composition according to claim 1, further comprising (F) an ethylenically unsaturated bond-containing resin.
12. The resin composition according to claim 1 , further comprising a thermoplastic resin (G).
13. 2. The resin composition according to claim 1, wherein, when tensile strength is measured in accordance with JIS K7127, the strength at break of the cured product of the resin composition is 100 MPa or more and the elongation at break of the cured product of the resin composition is 1.5% or more.
14. The resin composition according to claim 1, wherein the glass transition temperature (Tg) of the cured product of the resin composition is 140°C or higher.
15. The resin composition according to claim 1, wherein the dielectric loss tangent (Df) of a cured product of the resin composition is 0.004 or less when measured at 5.8 GHz and 23°C.
16. The resin composition according to claim 1, wherein the cured product of the resin composition has a relative dielectric constant (Dk) of 3.2 or less when measured at 5.8 GHz and 23°C.
17. A cured product of the resin composition according to any one of claims 1 to 16.
18. A resin sheet comprising a support and a resin composition layer formed from the resin composition according to any one of claims 1 to 16 provided on the support.
19. A printed wiring board comprising an insulating layer made of a cured product of the resin composition according to any one of claims 1 to 16.
20. A semiconductor device comprising the printed wiring board according to claim 19.
Citation Information
Patent Citations
Semiconductor sealing resin composition and semiconductor device
JP2015101669A
Resin composition for encapsulation, semiconductor device and on-vehicle electronic control unit
JP2017110051A
Resin composition, layered product, semiconductor chip with resin composition layer, substrate on which semiconductor chip with resin composition layer is to be mounted, and semiconductor device
WO2023063282A1
Radiation control building
JP1988079675A
Epoxy resin composition for semiconductor encapsulation, semiconductor device using the same, and semiconductor manufacturing method
JP2014521754A